Polytetrafluoroethylene Fine Powder

By producing PTFE fine powders under controlled conditions to minimize moisture and impurities, the issues of defects and environmental concerns in existing PTFE powders are addressed, resulting in improved homogeneity and compliance with sustainable standards.

JP7657762B2Active Publication Date: 2025-04-07DAIKIN INDUSTRIES LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022158883
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2022-09-30
Publication Date
2025-04-07
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The existing PTFE fine powders contain high levels of moisture and impurities, which lead to defects such as cracks in molded bodies and the emission of low molecular weight fluorine-containing compounds, including PFOA.

Method used

The development of PTFE fine powders that are substantially free of moisture and fluorine-containing compounds with a molecular weight of 1000 or less, achieved through a process involving extremely limited conditions during treatment, resulting in powders with a standard specific gravity of 2.160 or less and enhanced stretchability.

Benefits of technology

The resulting PTFE fine powders exhibit reduced moisture content to 0.010% by mass or less and minimal impurities, leading to improved homogeneity in molded bodies, reduced defects, and compliance with sustainable chemical substance management standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657762000001
    Figure 0007657762000001
  • Figure 0007657762000002
    Figure 0007657762000002
  • Figure 0007657762000003
    Figure 0007657762000003
Patent Text Reader

Abstract

To provide a polytetrafluoroethylene fine powder which is reduced in the moisture content and impurities.SOLUTION: The present disclosure provides a polytetrafluoroethylene fine powder which does not substantially contain moisture and a fluorine-containing compound having a molecular weight of 1,000 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to polytetrafluoroethylene fine powder. [Background technology]

[0002] Polytetrafluoroethylene (PTFE) fine powder is used for insulating tapes, covering materials for coaxial cables and oxygen sensors, and tubes for fuel and drinking water, etc., due to its excellent electrical insulation, water resistance, chemical resistance, heat resistance, and cleanability. These are manufactured by paste extrusion molding of PTFE fine powder. In recent years, there has been a trend toward weight reduction in various applications, and for example, thinner covering materials are required.

[0003] In addition, tapes obtained by paste extrusion of PTFE fine powder can be processed into porous materials by highly stretching them, allowing for the manufacture of water- and moisture-permeable membranes and filter media, which are used in a wide range of applications such as clothing, separation membranes, and air filters.

[0004] PTFE fine powder is produced by emulsion polymerization of tetrafluoroethylene (TFE).

[0005] Patent Document 1 describes a method for reducing thermally induced discoloration of a fluoropolymer resin by exposing the fluoropolymer resin obtained by emulsion polymerization using a hydrocarbon surfactant to an oxidizing agent. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2015-516029 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present disclosure is to provide a PTFE fine powder with reduced moisture and impurities. [Means for solving the problem]

[0008] The present disclosure (1) relates to a polytetrafluoroethylene fine powder that is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less.

[0009] The present disclosure (2) is the polytetrafluoroethylene fine powder of the present disclosure (1), which is substantially free of any of the fluorine-containing compounds represented by the following formulas: F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF 2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4 R is an optionally substituted imidazolium, an optionally substituted pyridinium, or an optionally substituted phosphonium. 1 is H or an organic group.

[0010] The present disclosure (3) is the polytetrafluoroethylene fine powder of the present disclosure (1) or (2), in which the content of the fluorine-containing compound is less than 25 ppb by mass based on the polytetrafluoroethylene fine powder.

[0011] The present disclosure (4) also relates to a polytetrafluoroethylene fine powder which is stretchable, has a standard specific gravity of 2.160 or less, and is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less.

[0012] The present disclosure (5) also relates to a polytetrafluoroethylene fine powder which is stretchable, has a standard specific gravity of 2.160 or less, and is substantially free of both moisture and a fluorine-containing compound represented by the following formula: F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF 2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4 R is an optionally substituted imidazolium, an optionally substituted pyridinium, or an optionally substituted phosphonium. 1 is H or an organic group.

[0013] The present disclosure (6) is the polytetrafluoroethylene fine powder of the present disclosure (4) or (5), in which the breaking strength measured using an elongated bead obtained in a stretching test at a total elongation rate of 2400% is 25.0 N or more and 70.0 N or less.

[0014] The present disclosure (7) is the polytetrafluoroethylene fine powder of the present disclosure (4) or (5), in which the breaking strength measured using an elongated bead obtained in a stretching test at a total elongation rate of 2400% is 10.0 N or more and less than 25.0 N.

[0015] The present disclosure (8) is the polytetrafluoroethylene fine powder of the present disclosure (4), (5), or (7), in which the extrusion pressure at a reduction ratio of 100 is 18 MPa or less.

[0016] The present disclosure (9) is a polytetrafluoroethylene fine powder in any combination with any of the present disclosures (4) to (8), in which the content of the fluorine-containing compound is less than 25 ppb by mass relative to the polytetrafluoroethylene fine powder.

[0017] The present disclosure (10) is a polytetrafluoroethylene fine powder having a moisture content of 0.010% by mass or less relative to the polytetrafluoroethylene fine powder, which is any combination with any of the present disclosures (4) to (9).

[0018] The present disclosure (11) is a polytetrafluoroethylene fine powder obtained by polymerization in the presence of a fluorine-containing surfactant in any combination with any of the present disclosures (4) to (10).

[0019] The present disclosure (12) is a polytetrafluoroethylene fine powder in any combination with any of the present disclosures (4) to (11) which are stretched materials.

[0020] The present disclosure (13) also relates to an extruded body using the polytetrafluoroethylene fine powder in any combination with any of the present disclosures (4) to (12).

[0021] The present disclosure (14) is a stretched body of the present disclosure (13) which is a porous membrane, a biaxially stretched membrane, or a filter medium.

[0022] The present disclosure (15) also relates to a modified polytetrafluoroethylene fine powder which is paste-extrudable, has a standard specific gravity of 2.135 to 2.200, and is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less.

[0023] The present disclosure (16) also relates to a modified polytetrafluoroethylene fine powder which is paste-extrudable, has a standard specific gravity of 2.135 to 2.200, and is substantially free of both moisture and a fluorine-containing compound represented by the following formula: F(CF 2 )7 COOM、 F(CF 2 ) 5 COOM、 H(CF 2 ) 6 COOM、 H(CF 2 ) 7 COOM、 CF 3 O(CF 2 ) 3 OCHFCF 2 COOM、 C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM、 C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF(CF3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4 R is an optionally substituted imidazolium, an optionally substituted pyridinium, or an optionally substituted phosphonium. 1 is H or an organic group.

[0024] The present disclosure (17) is the modified polytetrafluoroethylene fine powder of the present disclosure (15) or (16), in which the extrusion pressure at a reduction ratio of 1,500 is 15 to 80 MPa.

[0025] The present disclosure (18) is a modified polytetrafluoroethylene fine powder in any combination with any of the present disclosures (15) to (17), in which the content of the fluorine-containing compound is less than 25 ppb by mass relative to the modified polytetrafluoroethylene fine powder.

[0026] The present disclosure (19) is a polytetrafluoroethylene fine powder having a moisture content of 0.010% by mass or less relative to the modified polytetrafluoroethylene fine powder, which is any combination with any of the present disclosures (15) to (18).

[0027] The present disclosure (20) is a modified polytetrafluoroethylene fine powder obtained by polymerization in the presence of a fluorine-containing surfactant in any combination with any of the present disclosures (15) to (19).

[0028] The present disclosure (21) also relates to a molded article using the modified polytetrafluoroethylene fine powder in any combination with any of the present disclosures (15) to (20).

[0029] The present disclosure (22) is a molded article of the present disclosure (21) which is an electric wire covering material or a tube.

[0030] The present disclosure (23) also relates to a perfluorovinyl ether-modified polytetrafluoroethylene fine powder which can be paste-extruded, has a standard specific gravity of 2.135 to 2.200, and is substantially free of both moisture and the fluorine-containing compound represented by the general formula (2). General formula (2):[C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14; M + represents a cation.)

[0031] The present disclosure (24) is the modified polytetrafluoroethylene fine powder of the present disclosure (23), in which the amount of modification with perfluorovinyl ether is 0.02 mass% or more and 0.30 mass% or less.

[0032] The present disclosure (25) is the modified polytetrafluoroethylene fine powder of the present disclosure (23) or (24), in which the extrusion pressure at a reduction ratio of 1,500 is 15 to 80 MPa.

[0033] The present disclosure (26) is a modified polytetrafluoroethylene fine powder in any combination with any of the present disclosures (23) to (25), in which the total content of the fluorine-containing compounds is less than 25 ppb by mass based on the modified polytetrafluoroethylene fine powder. Effect of the Invention

[0034] According to the present disclosure, it is possible to provide a PTFE fine powder with reduced moisture and impurities. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Moisture and impurities in PTFE fine powder can cause problems in obtaining homogeneous molded products, such as cracks and defects. In recent years, there has also been a demand to reduce emissions of low molecular weight fluorine-containing compounds, including PFOA, as part of sustainable chemical substance management. As a result of extensive research, it was discovered that by processing under extremely specific conditions, it is possible to obtain PTFE fine powder with reduced moisture and certain impurities.

[0036] The present disclosure will now be described in detail.

[0037] The present disclosure provides a PTFE fine powder that is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less. The PTFE fine powder of the present disclosure is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1000 or less, and is therefore less susceptible to problems caused by residual moisture or the fluorine-containing compounds.

[0038] The PTFE fine powder of the present disclosure is substantially free of moisture. Substantially free of moisture means that the moisture content of the PTFE fine powder is 0.010% by mass or less. The water content is preferably 0.005% by mass or less, and more preferably 0.002% by mass or less. The water content is measured by the following method. The mass of the PTFE fine powder is measured before and after heating at 150°C for 2 hours, and calculated according to the following formula. Samples are taken three times, and the mass is calculated for each, and the average value is calculated and used. Moisture content (mass%) = [(mass (g) of PTFE fine powder before heating) - (mass (g) of PTFE fine powder after heating)] / (mass (g) of PTFE fine powder before heating) x 100

[0039] The PTFE fine powder of the present disclosure is substantially free of fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially free of fluorine-containing compounds having a molecular weight of not more than 1000" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0040] The amount of the fluorine-containing compound having a molecular weight of 1,000 or less is measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The resulting extract is concentrated using nitrogen purging as appropriate, and the fluorine-containing compounds in the concentrated extract are measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate fluorine-containing compound is confirmed. Prepare aqueous solutions with five or more levels of content of the standard substance, perform LC / MS analysis of the aqueous solutions with each content, plot the relationship between the content and the area for that content, and draw a calibration curve. Using the above calibration curve, the area of ​​the LC / MS chromatogram of the fluorine-containing compounds in the extract is converted to the content of the fluorine-containing compounds. The lower detection limit in this measurement method is 10 ppb by mass.

[0041] The amount of the fluorine-containing compound having a molecular weight of 1000 or less can also be measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment at 60°C for 2 hours. After standing at room temperature, remove the solids to obtain an extract. The resulting extract is appropriately concentrated with nitrogen purging, and the fluorine-containing compounds in the concentrated extract are measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate fluorine-containing compound is confirmed. Five levels of methanol standard solutions of fluorine-containing compounds with known concentrations are prepared, and measurements are performed using a liquid chromatograph mass spectrometer. A calibration curve is created using a first-order approximation from the methanol standard solution concentration and the peak integral value in each concentration range. The content of the fluorine-containing compound in the extract is measured from the above calibration curve, and the content of the fluorine-containing compound in the sample is converted. The detection limit in this measurement method is 1 ppb by mass.

[0042] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include a fluorine-containing compound having a hydrophilic group and a molecular weight of 1000 g / mol or less. The molecular weight of the fluorine-containing compound is preferably 800 or less, and more preferably 500 or less. Polymer particles obtained by polymerization in the presence of a fluorine-containing surfactant usually contain a fluorine-containing surfactant in addition to PTFE. In this specification, the fluorine-containing surfactant is one that is used during polymerization. The above-mentioned fluorine-containing compound having a molecular weight of 1000 or less may be a compound that is not added during polymerization, for example, a compound that is generated as a by-product during polymerization. In addition, when the fluorine-containing compound having a molecular weight of 1000 or less contains an anionic moiety and a cationic moiety, it means a compound containing fluorine in which the molecular weight of the anionic moiety is 1000 or less. The fluorine-containing compound having a molecular weight of 1000 or less does not include PTFE.

[0043] Examples of the hydrophilic group include -COOM and -SO 2 M or -SO 3 M, -COOM, -SO 3 M (In each formula, M is H, metal atom, NR 14 , optionally substituted imidazolium, optionally substituted pyridinium or optionally substituted phosphonium; R 1 is H or an organic group.

[0044] As the fluorine-containing surfactant, a surfactant containing fluorine in the anionic part having a molecular weight of 1000 or less (anionic fluorine-containing surfactant) can also be used. The "anionic part" refers to the part of the fluorine-containing surfactant excluding the cation. For example, F(CF 2 ) n1 In the case of COOM, "F(CF 2 ) n1 The "COO" part. The anionic fluorine-containing surfactant may be a surfactant represented by the following general formula (N 0 ): X n0 -Rf n0 -Y 0 (N 0 ) (In the formula, X n0 is H, Cl or F. n0 Y is a linear, branched or cyclic alkylene group having 3 to 20 carbon atoms, in which some or all of the H's are substituted with F, and the alkylene group may contain one or more ether bonds, and some of the H's may be substituted with Cl. 0 is an anionic group. Y 0 The anionic groups are -COOM, -SO 2 M or -SO 3 M, -COOM or -SO 3 It can be M. M is H, a metal atom, or NR 1 4 , optionally substituted imidazolium, optionally substituted pyridinium or optionally substituted phosphonium; R 1 is H or an organic group. The metal atom includes alkali metals (Group 1), alkaline earth metals (Group 2), etc., such as Na, K, or Li. R 1 As the 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be: M is H, a metal atom or NR 1 4 may be H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4 may be H, Na, K, Li or NH 4 It may be. Above Rf n0 may be one in which 50% or more of H is substituted with fluorine.

[0045] The above fluorine-containing surfactant may be one type of fluorine-containing surfactant, or a mixture containing two or more types of fluorine-containing surfactants.

[0046] Examples of the fluorine-containing surfactant include compounds represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF 2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4 R is an optionally substituted imidazolium, an optionally substituted pyridinium, or an optionally substituted phosphonium. 1 is H or an organic group. The PTFE fine powder of the present disclosure preferably does not substantially contain any of the fluorine-containing compounds represented by the above formulas.

[0047] In each of the above formulas, M is H, a metal atom, or NR 1 4 may be H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4 may be H, Na, K, Li or NH 4 It may be. R 1 is H or C 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be:

[0048] When the PTFE fine powder of the present disclosure is substantially free of any of the fluorine-containing compounds represented by the above formulas, the occurrence of problems due to the remaining fluorine-containing compounds can be suppressed. "Substantially free of any of the fluorine-containing compounds represented by the above formulas" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 ppb by mass, and more preferably 10 ppb by mass or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0049] The emulsion-polymerized particles obtained by polymerizing monomers such as TFE and modified monomers may contain, in addition to PTFE, a fluorine-containing compound produced by polymerization of the monomer. The above-mentioned fluorine-containing compound having a molecular weight of 1000 or less (or a fluorine-containing compound having a hydrophilic group having a molecular weight of 1000 g / mol or less) also includes such a fluorine-containing compound produced by polymerization of the monomer.

[0050] In one embodiment of the emulsion polymerized particles, the compound represented by the following general formula (1) is contained as the fluorine-containing compound having a hydrophilic group. General formula (1):[X-Rf 11 -A - ] i Y i+ (Wherein, X is H, Cl, Br, F or I, Rf 11 represents a linear or branched partially or fully fluorinated aliphatic group, or a linear or branched partially or fully fluorinated aliphatic group interrupted by at least one oxygen atom; A - is the acid group, Y i+ represents a cation having a valence i, where i is an integer from 1 to 3.

[0051] In one embodiment of the emulsion polymerized particles, the compound represented by the following general formula (2) is contained as the fluorine-containing compound having a hydrophilic group. General formula (2):[C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14, preferably an integer of 9 to 12; M + represents a cation.)

[0052] It is known that the compound represented by general formula (2) (perfluoroalkanoic acid) is formed during polymerization when perfluoroalkyl vinyl ether or the like is used as a modified monomer (see WO 2019 / 161153).

[0053] In one embodiment of the emulsion polymerized particles, the compound represented by the following general formula (3) is contained as the fluorine-containing compound having a hydrophilic group. General formula (3):[R 31 -OL-CO 2 - ]M + (In the formula, R 31 represents a linear or branched partially or fully fluorinated aliphatic group, or a linear or branched partially or fully fluorinated aliphatic group interrupted by at least one oxygen atom; L represents a linear or branched non-fluorinated, partially fluorinated or fully fluorinated alkylene group; M+ represents a cation.)

[0054] In one embodiment of the emulsion polymerized particles, the compound represented by the general formula (4) is contained as the fluorine-containing compound having a hydrophilic group. General formula (4):[H-(CF 2 ) m CO 2 - ]M + (In the formula, m is an integer of 3 to 19, M + represents a cation.)

[0055] M constituting the cation in the above formula may be the same as M described above.

[0056] The PTFE fine powder of the present disclosure preferably does not substantially contain the fluorine-containing compound represented by the above general formula (2), and more preferably does not substantially contain any of the fluorine-containing compounds represented by the above general formulas (1) to (4), thereby making it possible to suppress the occurrence of problems caused by the remaining fluorine-containing compounds. "Substantially free of the fluorine-containing compound represented by the above general formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0057] It is also preferable that the PTFE fine powder of the present disclosure does not substantially contain a hydrocarbon surfactant. This can suppress the occurrence of problems caused by the residual hydrocarbon surfactant. It is preferable that the hydrocarbon surfactant does not contain a fluorine atom. "Substantially free of hydrocarbon surfactant" means that the amount of the hydrocarbon surfactant is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the hydrocarbon surfactant is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0058] The amount of the hydrocarbon surfactant is measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and ultrasonicate for 60 minutes to obtain an extract. The resulting extract is concentrated using nitrogen purging as appropriate, and the hydrocarbon surfactant in the concentrated extract is measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate hydrocarbon surfactant is confirmed. Prepare aqueous solutions with five or more levels of content of the standard substance, perform LC / MS analysis of the aqueous solutions with each content, plot the relationship between the content and the area for that content, and draw a calibration curve. Using the above calibration curve, convert the area of ​​the LC / MS chromatogram of the hydrocarbon surfactant in the extract into the content of the hydrocarbon surfactant. The lower detection limit in this measurement method is 10 ppb by mass.

[0059] The amount of the hydrocarbon surfactant can also be measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment at 60°C for 2 hours. After leaving it to stand at room temperature, remove the solids to obtain an extract. The resulting extract is concentrated with an appropriate nitrogen purge, and the hydrocarbon surfactant in the concentrated extract is measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate hydrocarbon surfactant is confirmed. Five levels of methanol standard solutions of hydrocarbon surfactants with known concentrations are prepared, and measurements are performed using a liquid chromatograph mass spectrometer. A calibration curve is created using a first-order approximation from the methanol standard solution concentration and the peak integral value in each concentration range. The content of the hydrocarbon surfactant in the extract is measured from the above calibration curve, and the content of the hydrocarbon surfactant in the sample is converted. The detection limit in this measurement method is 1 ppb by mass.

[0060] The PTFE fine powder of the present disclosure preferably does not substantially contain a polymer (I) (excluding PTFE) containing a polymerization unit (I) based on a monomer (I) represented by general formula (I). CX 1 X 3 =CX 2 R 11 (-CZ 1 Z 2 -A 0 ) m (I) (In the formula, X 1 and X 3 are each independently F, Cl, H or CF 3 ;X 2 is H, F, an alkyl group or a fluorine-containing alkyl group; A 0 is an anionic group; R 11 is a linking group; Z 1 and Z 2 are each independently H, F, an alkyl group or a fluorine-containing alkyl group; and m is an integer of 1 or more. The polymer (I) contains two or more polymerized units (I).

[0061] A 0In addition to anionic groups such as sulfate and carboxylate groups, the anionic groups include acid groups such as -COOH, -COONH 4 The anionic group includes a functional group that provides an anionic group such as an acid salt group, such as a sulfate group, a carboxylate group, a phosphate group, a phosphonate group, a sulfonate group, or a -C(CF 3 ) 2 OM (wherein M is -H, a metal atom, -NR 1 4 , optionally substituted imidazolium, optionally substituted pyridinium or optionally substituted phosphonium; R 1 is H or an organic group.) is preferred, with a sulfate group, a carboxylate group, a phosphate group, a phosphonate group or a sulfonate group being more preferred.

[0062] The polymer (I) may contain only polymerization units (I) based on one type of monomer represented by general formula (I), or may contain polymerization units (I) based on two or more types of monomers represented by general formula (I).

[0063] R 11 is a linking group. The linking group is an (m+1)-valent linking group, and when m is 1, it is a divalent linking group. The linking group may be a single bond, and preferably contains at least one carbon atom, and the number of carbon atoms may be 2 or more, 4 or more, 8 or more, 10 or more, or 20 or more. There is no upper limit, but it may be, for example, 100 or less, or 50 or less.

[0064] The linking group may be linear or branched, cyclic or acyclic in structure, saturated or unsaturated, substituted or unsubstituted, and may optionally contain one or more heteroatoms selected from the group consisting of sulfur, oxygen, and nitrogen, and may optionally contain one or more functional groups selected from the group consisting of esters, amides, sulfonamides, carbonyls, carbonates, urethanes, ureas, and carbamates. The linking group may not contain carbon atoms, but may be a catenary heteroatom such as oxygen, sulfur, or nitrogen.

[0065] The number average molecular weight of the polymer (I) is 0.1×10 4 or more, and 75.0×10 4 It may be the following:

[0066] The weight average molecular weight of the polymer (I) is 0.2×10 4 or more, and 150.0×10 4 It may be the following:

[0067] "Substantially free of polymer (I)" means that the amount of polymer (I) is 25 ppb by mass or less based on the PTFE fine powder. The amount of the polymer (I) is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0068] The amount of the polymer (I) is measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The obtained extract is appropriately concentrated with a nitrogen purge, and the polymer (I) in the concentrated extract is measured by LC / MS / MS. The lower detection limit in this measurement method is 10 ppb by mass.

[0069] The amount of the polymer (I) can also be measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment at 60°C for 2 hours. After standing at room temperature, remove the solids to obtain an extract. The obtained extract is appropriately concentrated with nitrogen purging, and the polymer (I) in the concentrated extract is measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate polymer (I) is confirmed. Five levels of methanol standard solutions of polymer (I) with known concentrations are prepared, and measurements are performed using a liquid chromatograph mass spectrometer. A calibration curve is created using a first-order approximation from the methanol standard solution concentration and the peak integral value in each concentration range. The content of polymer (I) contained in the extract is measured from the above calibration curve, and the content of polymer (I) contained in the sample is converted. The detection limit in this measurement method is 1 ppb by mass.

[0070] In view of excellent extensibility, the PTFE fine powder of the present disclosure preferably has a standard specific gravity (SSG) of 2.200 or less, more preferably 2.180 or less, even more preferably 2.170 or less, even more preferably 2.160 or less, even more preferably 2.150 or less, especially preferably 2.145 or less, and particularly preferably 2.140 or less. The SSG is also preferably equal to or greater than 2.130. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.

[0071] The PTFE fine powder of the present disclosure has an average primary particle size of preferably 350 nm or less, more preferably 330 nm or less, even more preferably 320 nm or less, even more preferably 300 nm or less, especially preferably 280 nm or less, and particularly preferably 250 nm or less, and preferably 100 nm or more, more preferably 150 nm or more, even more preferably 170 nm or more, and particularly preferably 200 nm or more. The average primary particle size is measured by the following method. The PTFE aqueous dispersion is diluted with water until the solid content is 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph are measured to create a calibration curve. Using this calibration curve, the number-average particle diameter is determined from the measured transmittance of the 550 nm projected light of each sample, and is taken as the average primary particle diameter.

[0072] The PTFE fine powder of the present disclosure may have an average secondary particle size of 350 μm or more, preferably 400 μm or more, more preferably 450 μm or more, even more preferably 500 μm or more, even more preferably 550 μm or more, and especially preferably 600 μm or more, and preferably 1000 μm or less, more preferably 900 μm or less, even more preferably 800 μm or less, and even more preferably 700 μm or less. The average secondary particle size is measured in accordance with JIS K 6891.

[0073] The PTFE fine powder of the present disclosure may have an extrusion pressure at a reduction ratio (RR) of 100 of 5 MPa or more, preferably 10 MPa or more, more preferably 12 MPa or more, even more preferably 15 MPa or more, and even more preferably 17 MPa or more. In terms of improving processability, the extrusion pressure in RR100 is preferably 50 MPa or less, more preferably 40 MPa or less, even more preferably 30 MPa or less, even more preferably 25 MPa or less, even more preferably 23 MPa or less, even more preferably 21 MPa or less, and particularly preferably 20 MPa or less.

[0074] The PTFE fine powder of the present disclosure has an extrusion pressure in RR1600 of preferably 20 MPa or more, more preferably 25 MPa or more, and even more preferably 30 MPa or more. In terms of improving processability, the extrusion pressure in RR1600 is preferably 60 MPa or less, and more preferably 50 MPa or less.

[0075] The extrusion pressure in RR100 is measured by the following method. 50 g of PTFE powder is mixed with 10.25 g of hydrocarbon oil (trade name: Isopar E, Exxon Chemical) as an extrusion aid in a polyethylene container for 3 minutes. The above mixture is filled into the cylinder of an extruder at room temperature (25±2°C), and a load of 0.47 MPa is applied to the piston inserted in the cylinder and held for 1 minute. The mixture is then extruded from the orifice at a ram speed of 18 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice is 100. In the latter half of the extrusion operation, the load (N) when the pressure reaches equilibrium is divided by the cross-sectional area of ​​the cylinder to determine the extrusion pressure (MPa).

[0076] The extrusion pressure in RR1600 is measured by the following method. 50 g of PTFE powder is mixed with 10.25 g of hydrocarbon oil (trade name: Isopar G, Exxon Chemical) as an extrusion aid in a polyethylene container for 3 minutes. The mixture is filled into the cylinder of an extruder at room temperature (25±2°C), and a load of 1.2 MPa is applied to the piston inserted in the cylinder and held for 1 minute. The mixture is then extruded from the orifice at a ram speed of 18 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice is 1600. In the latter half of the extrusion operation, the load (N) when the pressure reaches equilibrium is divided by the cross-sectional area of ​​the cylinder to determine the extrusion pressure (MPa).

[0077] The PTFE fine powder of the present disclosure is preferably extensible. Being extensible means that an extensible body can be obtained in the following extensibility test. The bead obtained by the above paste extrusion with RR100 is dried at 230°C for 30 minutes to remove the lubricant. The dried bead is cut to an appropriate length, placed in an oven heated to 300°C, and stretched in the oven at an extension speed of 100% / sec.

[0078] The PTFE fine powder of the present disclosure has excellent extensibility and is preferably extensible up to 25 times. Whether or not the film can be stretched 25 times can be confirmed by the following stretching test. The bead obtained by the above paste extrusion with RR100 is dried at 230°C for 30 minutes to remove the lubricant. The dried bead is cut to an appropriate length and placed in an oven heated to 300°C. In the oven, it is stretched at an extension rate of 100% / sec until it becomes 25 times its length before the extension test. If it does not break during extension, it is judged to be able to be stretched to 25 times.

[0079] The PTFE fine powder of the present disclosure preferably has a breaking strength of 20.0 N or more, more preferably 25.0 N or more, even more preferably 30.0 N or more, even more preferably 32.0 N or more, and even more preferably 35.0 N or more. The higher the breaking strength, the better, but it may be 100.0 N or less, 80.0 N or less, or 50.0 N or less. The breaking strength is a value determined by the following method. The stretched bead (produced by stretching the bead) obtained in the above 25-fold stretching test is clamped and fixed in a movable jaw having a gauge length of 5.0 cm, and a tensile test is carried out at 25°C and a speed of 300 mm / min. The strength at the time of break is measured as the breaking strength.

[0080] In terms of lowering the extrusion pressure, increasing the breaking strength, and improving the heat resistance, the PTFE fine powder of the present disclosure preferably has a thermal instability index (TII) of less than 40, more preferably 15 or less, even more preferably 10 or less, and particularly preferably less than 5. The thermal instability index is also preferably −10 or more, and more preferably 0 or more. The heat instability index is measured in accordance with ASTM D 4895.

[0081] In terms of excellent handleability, the PTFE fine powder of the present disclosure may have an average aspect ratio of 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, even more preferably 1.6 or less, even more preferably 1.5 or less, even more preferably 1.4 or less, especially preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. The average aspect ratio may also be 1.0 or more. The above average aspect ratio is determined by observing PTFE powder or an aqueous PTFE dispersion diluted to a solid content of approximately 1% by mass with a scanning electron microscope (SEM), processing the images of 200 or more particles randomly selected, and averaging the ratio of the long axis to the short axis.

[0082] From the viewpoint of excellent handleability, the PTFE fine powder of the present disclosure has an apparent density of preferably 0.40 g / ml or more, more preferably 0.43 g / ml or more, even more preferably 0.45 g / ml or more, even more preferably 0.48 g / ml or more, and particularly preferably 0.50 g / ml or more. The upper limit is not particularly limited, but may be 0.70 g / ml. The apparent density is measured in accordance with JIS K 6892.

[0083] The PTFE fine powder of the present disclosure preferably has non-melt secondary processability. The non-melt secondary processability means a property that the melt flow rate cannot be measured at a temperature higher than the melting point in accordance with ASTM D-1238 and D-2116, in other words, a property that does not flow easily even in the melting temperature range.

[0084] The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0 mass% or more of TFE units and 1.0 mass% or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units. The above-mentioned PTFE is preferably the above-mentioned modified PTFE.

[0085] In terms of improving stretchability, the modified PTFE preferably has a modified monomer unit content in the range of 0.00001 to 1.0% by mass relative to the total polymerized units. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, even more preferably 0.20% by mass, even more preferably 0.15% by mass, even more preferably 0.10% by mass, even more preferably 0.08% by mass, especially preferably 0.05% by mass, and most preferably 0.03% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0086] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0087] The modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene, perfluorovinyl ethers, perfluoroallyl ethers, vinyl heterocyclic compounds such as perfluoro-2,2-dimethyl-1,3-dioxole [PDD], (perfluoroalkyl)ethylenes, ethylene, etc. The modified monomers used may be one type or multiple types.

[0088] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF 2 =CF-ORf (A) (wherein Rf represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0089] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rf in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0090] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0091] The perfluorovinyl ether further includes those in which Rf in the above general formula (A) is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rf is the following formula:

[0092] [ka]

[0093] (wherein m represents 0 or an integer of 1 to 4), Rf is a group represented by the following formula:

[0094] [ka]

[0095] (wherein n represents an integer of 1 to 4).

[0096] The (perfluoroalkyl)ethylene (PFAE) is not particularly limited, and examples thereof include (perfluorobutyl)ethylene (PFBE) and (perfluorohexyl)ethylene.

[0097] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF 2 =CF-CF 2 -ORf 1 (B) (In the formula, Rf 1 represents a perfluoro organic group.

[0098] Above Rf 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. 2 =CF-CF 2 -O-CF 3 , C.F. 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC4 F 9 At least one selected from the group consisting of CF 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 More preferably, at least one selected from the group consisting of CF 2 =CF-CF 2 -O-CF 2 CF 2 CF 3 is more preferred.

[0099] The modifying monomer is preferably at least one selected from the group consisting of PAVE and HFP, and more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE) and HFP, in terms of improving stretchability.

[0100] As the above-mentioned modified monomer, in terms of lowering the extrusion pressure and increasing the breaking strength, at least one selected from the group consisting of VDF, HFP, CTFE and PAVE is preferable, and at least one selected from the group consisting of VDF, HFP and CTFE is more preferable. From the viewpoint of improving heat resistance, it is one of the preferred embodiments that the PTFE contains TFE units, VDF units and HFP units, and the total amount of the VDF units and the HFP units is 1.0 mass % or less based on the total polymerized units.

[0101] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.

[0102] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.

[0103] The PTFE fine powder of the present disclosure preferably does not substantially contain organic solvents. "Substantially does not contain organic solvents" means that the organic solvent content in the PTFE fine powder is 5% by mass or less. The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.

[0104] The PTFE fine powder of the present disclosure can be suitably produced by a production method including, for example, a step (A) of preparing an aqueous dispersion of PTFE, a step (B) of coagulating the aqueous dispersion to obtain a wet powder of PTFE, and a step (C) of placing the wet powder in a container whose bottom and / or sides are breathable and heat-treating it at a temperature of 130 to 300°C for 2 hours or more to obtain a PTFE fine powder. The present disclosure also provides a method for producing the above.

[0105] The aqueous dispersion in step (A) can be produced, for example, by emulsion polymerization.

[0106] The emulsion polymerization can be carried out by a known method. For example, in the presence of an anionic fluorine-containing surfactant and a polymerization initiator, the emulsion polymerization of the monomers required for forming the PTFE is carried out in an aqueous medium to obtain an aqueous dispersion containing the PTFE particles (primary particles). In the emulsion polymerization, a chain transfer agent, a buffer, a pH adjuster, a stabilizing assistant, a dispersion stabilizer, a radical scavenger, etc. may be used as necessary.

[0107] The aqueous dispersion may contain at least one of the above-mentioned fluorine-containing compounds.

[0108] The above step (A) may be a step of emulsion polymerizing TFE and, if necessary, a modifying monomer.

[0109] The above emulsion polymerization can be carried out, for example, in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator. The emulsion polymerization can be carried out by charging an aqueous medium, the anionic fluorine-containing surfactant, monomers and, if necessary, other additives into a polymerization reactor, stirring the contents of the reactor, maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of polymerization initiator to initiate the polymerization reaction. After the start of the polymerization reaction, monomers, polymerization initiators, chain transfer agents, the surfactants and the like may be additionally added depending on the purpose.

[0110] The polymerization initiator is not particularly limited as long as it can generate radicals within the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it can also be combined with a reducing agent or the like to initiate polymerization as a redox. The concentration of the polymerization initiator is appropriately determined depending on the type of monomer, the molecular weight of the desired PTFE, and the reaction rate.

[0111] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0112] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and disec-butyl peroxydicarbonate, peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate, dialkyl peroxides such as di-t-butyl peroxide, and the like. In addition, di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecafluorononanoyl) peroxide, di(perfluorobutyryl) peroxide, di(perfluorovaleryl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide, di(perfluorononanoyl) peroxide, di(ω-chloro Representative examples include di[perfluoro(or fluorochloro)acyl]peroxides such as di(ω-hexafluorobutyryl) peroxide, di(ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorodotriacontafluorodocosanoyl) peroxide.

[0113] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, sodium salts, t-butyl permaleate, t-butyl hydroperoxide, disuccinic acid peroxide, etc., of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, etc. Among these, ammonium persulfate and disuccinic acid peroxide are preferred. A reducing agent such as sulfites and sulfites may also be included, and the amount used may be 0.1 to 20 times that of the peroxide.

[0114] The amount of the water-soluble radical polymerization initiator to be added is not particularly limited, but may be added all at once, stepwise, or continuously in an amount (e.g., several ppm relative to water concentration) at least to the extent that the polymerization rate does not decrease significantly. The upper limit is a range in which the reaction temperature may be increased while removing heat from the equipment side by the polymerization reaction heat, and a more preferable upper limit is a range in which the polymerization reaction heat can be removed from the equipment side. In terms of easily obtaining the above-mentioned physical properties, the amount of the polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, and is preferably an amount equivalent to 100 ppm or less, more preferably an amount equivalent to 10 ppm or less, relative to the aqueous medium.

[0115] For example, when polymerization is carried out at a low temperature of 30° C. or less, it is preferable to use a redox initiator that combines an oxidizing agent and a reducing agent as the polymerization initiator. Examples of the oxidizing agent include persulfates, organic peroxides, potassium permanganate, manganese triacetate, cerium ammonium nitrate, and bromates. Examples of the reducing agent include sulfites, bisulfites, bromates, diimines, and oxalic acid. Examples of the persulfates include ammonium persulfate and potassium persulfate. Examples of the sulfites include sodium sulfite and ammonium sulfite. In order to increase the decomposition rate of the initiator, it is also preferable to add a copper salt or an iron salt to the combination of the redox initiator. Examples of the copper salt include copper(II) sulfate, and examples of the iron salt include iron(II) sulfate.

[0116] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, a persulfate, manganese triacetate, a cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof, or a diimine. More preferably, the oxidizing agent is permanganic acid or a salt thereof, a persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.

[0117] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate. When a redox initiator is used, either the oxidizing agent or the reducing agent may be charged in advance in a polymerization tank, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferable to charge ammonium oxalate in a polymerization tank and continuously add potassium permanganate thereto. In this specification, when the redox initiator is described as "potassium permanganate / ammonium oxalate," it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.

[0118] The redox initiator is particularly preferably a combination of an oxidizing agent that is a salt and a reducing agent that is a salt. For example, the oxidizing agent which is the salt is more preferably at least one selected from the group consisting of persulfates, permanganates, cerium (IV) salts, and bromates, further preferably permanganates, and particularly preferably potassium permanganate. The reducing agent which is the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.

[0119] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate, and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, and cerium ammonium nitrate / ammonium oxalate, and even more preferably potassium permanganate / oxalic acid.

[0120] When a redox initiator is used, the oxidizing agent and the reducing agent may be added all at once at the beginning of the polymerization, the reducing agent may be added all at once at the beginning of the polymerization and the oxidizing agent may be added continuously, the oxidizing agent may be added all at once at the beginning of the polymerization and the reducing agent may be added continuously, or both the oxidizing agent and the reducing agent may be added continuously.

[0121] When one of the above redox polymerization initiators is added at the beginning of the polymerization and the other is added continuously, it is preferable to gradually reduce the rate of addition in order to obtain PTFE with a low SSG, and it is further preferable to stop the addition midway through the polymerization, and the timing for stopping the addition is preferably before 20 to 40 mass % of the total TFE consumed in the polymerization reaction is consumed.

[0122] When using a redox initiator as a polymerization initiator, the amount of oxidizing agent added to the aqueous medium is preferably 0.1 ppm or more, more preferably 0.3 ppm or more, more preferably 0.5 ppm or more, even more preferably 1 ppm or more, particularly preferably 5 ppm or more, and particularly preferably 10 ppm or more, and also preferably 10000 ppm or less, more preferably 1000 ppm or less, more preferably 100 ppm or less, and even more preferably 10 ppm or less. The amount of reducing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, more preferably 3 ppm or more, more preferably 5 ppm or more, particularly preferably 10 ppm or more, and also preferably 10000 ppm or less, more preferably 1000 ppm or less, more preferably 100 ppm or less, and even more preferably 10 ppm or less. When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100° C. or lower, more preferably 95° C. or lower, and even more preferably 90° C. or lower. The polymerization temperature is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher.

[0123] As the polymerization initiator, a water-soluble radical polymerization initiator and a redox initiator are preferred in that the above-mentioned properties can be easily obtained.

[0124] The aqueous medium is a reaction medium for polymerization, and refers to a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and, for example, a fluorine-free organic solvent such as an alcohol, ether, or ketone, and / or a fluorine-containing organic solvent having a boiling point of 40° C. or less.

[0125] In the above emulsion polymerization, a nucleating agent, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposer for the polymerization initiator, a dicarboxylic acid, and the like may be used, if necessary.

[0126] The emulsion polymerization is preferably carried out with the addition of a nucleating agent for the purpose of adjusting the particle size. The nucleating agent is preferably added before the start of the polymerization reaction. As the nucleating agent, a known agent can be used. For example, it is preferable that the nucleating agent is at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents, and it is more preferable that the nucleating agent is a nonionic surfactant.

[0127] The fluoropolyether may, for example, be a perfluoropolyether (PFPE) acid or a salt thereof. The perfluoropolyether (PFPE) acid or salt thereof may have any chain structure in which oxygen atoms in the backbone of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. Also, two or more types of fluorocarbon groups may be present in the molecule. A representative structure has a repeating unit represented by the following formula: (-CFCF 3 -CF 2 -O-) n (-CF 2 -CF 2 -CF 2 -O-) n (-CF 2 -CF 2 -O-) n -(-CF 2 -O-) m (-CF 2 -CFCF 3 -O-) n -(-CF 2 -O-) m

[0128] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed therein, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. The PFPE acid or its salt may also have a sulfonic acid, phosphonic acid group or their salt at one or both ends. The PFPE acid or its salt may also have a different group at each end. For monofunctional PFPEs, the other end of the molecule is usually perfluorinated, but may contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least two ether oxygens, preferably at least four ether oxygens, and even more preferably at least six ether oxygens. Preferably, at least one of the fluorocarbon groups separating the ether oxygens, more preferably at least two of such fluorocarbon groups, has two or three carbon atoms. Even more preferably, at least 50% of the fluorocarbon groups separating the ether oxygens have 2 or 3 carbon atoms. Also preferably, the PFPE acid or salt thereof has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure above is at least 5. Two or more of the PFPE acids or salts thereof having an acid group at one or both termini may be used in the manufacturing method of the present disclosure. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.

[0129] The emulsion polymerization is preferably carried out by adding a radical scavenger or a decomposer of the polymerization initiator, since it can further increase the molecular weight of PTFE and improve the stretchability. The radical scavenger or the decomposer of the polymerization initiator is preferably added after the start of the polymerization reaction, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and preferably before 50% by mass or less, preferably 40% by mass or less is polymerized. When depressurization and repressurization are performed as described below, it is preferable to add it after that.

[0130] The radical scavenger is a compound that does not have the ability to restart after addition or chain transfer to the free radical in the polymerization system. Specifically, a compound that easily undergoes a chain transfer reaction with a primary radical or a growing radical, and then generates a stable radical that does not react with a monomer, or a compound that easily undergoes an addition reaction with a primary radical or a growing radical, and generates a stable radical, is used. Generally, the activity of what is called a chain transfer agent is characterized by the chain transfer constant and the reinitiation efficiency, but among chain transfer agents, those with a reinitiation efficiency of almost 0% are called radical scavengers. The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero percent. "Reinitiation efficiency is substantially zero percent" means that the generated radicals turn the radical scavenger into stable radicals. Preferably, the compound has a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) of more than 0.1. The above compound has a chain transfer constant (Cs) of more preferably 0.5 or more, even more preferably 1.0 or more, even more preferably 5.0 or more, and particularly preferably 10 or more.

[0131] Examples of the radical scavengers include aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl 2 ) is preferably at least one selected from the group consisting of Examples of the aromatic hydroxy compound include unsubstituted phenol, polyhydric phenol, salicylic acid, m- or p-salicylic acid, gallic acid, and naphthol. The unsubstituted phenols include o-, m-, or p-nitrophenol, o-, m-, or p-aminophenol, p-nitrosophenol, etc. The polyhydric phenols include catechol, resorcinol, hydroquinone, pyrogallol, phloroglucinol, naphthresorcinol, etc. Examples of aromatic amines include o-, m- or p-phenylenediamine, benzidine, and the like. Examples of the quinone compound include o-, m- or p-benzoquinone, 1,4-naphthoquinone, alizarin, and the like. Thiocyanates include ammonium thiocyanate (NH 4 Examples include potassium thiocyanate (KSCN), sodium thiocyanate (NaSCN), etc. Of the above radical scavengers, aromatic hydroxy compounds are preferred, unsubstituted phenols or polyhydric phenols are more preferred, and hydroquinone is even more preferred.

[0132] The amount of the radical scavenger added is preferably an amount equivalent to 3 to 500% (molar basis) of the polymerization initiator concentration from the viewpoint of appropriately reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).

[0133] The decomposer for the polymerization initiator may be any compound capable of decomposing the polymerization initiator used, and is preferably at least one selected from the group consisting of sulfites, bisulfites, bromates, diimines, diimine salts, oxalic acid, oxalates, copper salts, and iron salts. Examples of sulfites include sodium sulfite and ammonium sulfite. Examples of copper salts include copper(II) sulfate, and examples of iron salts include iron(II) sulfate. The amount of the decomposition agent added is preferably an amount equivalent to 3 to 500% (molar basis) of the initiator concentration from the viewpoint of appropriately reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).

[0134] The emulsion polymerization may be carried out in the presence of 5 to 500 ppm of dicarboxylic acid relative to the aqueous medium in order to reduce the amount of coagulation produced during polymerization, and is preferably carried out in the presence of 10 to 200 ppm of dicarboxylic acid. If the amount of dicarboxylic acid is too small relative to the aqueous medium, sufficient effects may not be obtained, and if the amount is too large, a chain transfer reaction may occur, resulting in a low molecular weight polymer. The amount of dicarboxylic acid is more preferably 150 ppm or less. The dicarboxylic acid may be added before the start of the polymerization reaction or during the polymerization.

[0135] The dicarboxylic acid is preferably, for example, one represented by the general formula: HOOCRCOOH (wherein R represents an alkylene group having 1 to 5 carbon atoms), more preferably succinic acid, malonic acid, glutaric acid, adipic acid, or pimelic acid, and even more preferably succinic acid.

[0136] In the above emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined depending on the type of monomer used, the molecular weight of the target PTFE, and the reaction rate. Usually, the polymerization temperature is 5 to 150°C, preferably 10°C or higher, more preferably 30°C or higher, and even more preferably 50°C or higher. Also, it is more preferably 120°C or lower, and even more preferably 100°C or lower. The polymerization pressure is 0.05 to 10 MPaG. The polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. Also, the polymerization pressure is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.

[0137] When VDF is used as the modified monomer, in the emulsion polymerization, the VDF concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, in order to easily obtain the above-mentioned physical properties. The concentration may be 15 mol% or less, preferably 6.0 mol% or less, more preferably 5.0 mol% or less, even more preferably 3.0 mol% or less, and particularly preferably 1.0 mol% or less. The VDF concentration may be maintained until the end of the polymerization reaction, or depressurization may be performed during the reaction. It is preferable to charge VDF all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0138] When VDF is used as the modifying monomer, it is preferable not to release the pressure in the emulsion polymerization after VDF is charged into the polymerization vessel until the polymerization is completed. This allows VDF to remain in the system until the end of the polymerization, and the breaking strength of the obtained PTFE can be further increased.

[0139] When HFP is used as a modified monomer, in the emulsion polymerization, the HFP concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.01 to 3.0 mol % in order to easily obtain the above-mentioned properties. Furthermore, the HFP concentration in the gas in the reactor at the time when 40 mass % of the total TFE consumed in the polymerization reaction is polymerized is preferably greater than 0 mol % and 0.2 mol % or less. The above HFP concentration is preferably maintained until the end of the polymerization reaction. HFP may be charged all at once before the start of polymerization, or a portion may be charged before the start of polymerization and added continuously or intermittently after the start of polymerization. By allowing HFP to remain until the end of the polymerization reaction, the extrusion pressure is reduced despite the high breaking strength of the resulting PTFE.

[0140] When HFP is used as the modifying monomer, in the above emulsion polymerization, it is preferable to release the pressure before 5 to 40 mass % of the total TFE consumed in the polymerization reaction is polymerized, and then re-pressurize using only TFE, in order to further improve the breaking strength of the resulting PTFE. The pressure reduction is preferably carried out so that the pressure inside the reactor is 0.2 MPaG or less, more preferably 0.1 MPaG or less, and even more preferably 0.05 MPaG or less. Also, it is preferably carried out so that the pressure inside the reactor is 0.0 MPaG or more. The above pressure reduction and re-increase may be carried out several times. The pressure reduction may be carried out until the pressure is reduced using a vacuum pump.

[0141] When CTFE is used as the modified monomer, in the emulsion polymerization, the CTFE concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, in order to easily obtain the above-mentioned properties. The above concentration is also preferably 3.0 mol% or less, more preferably 1.0 mol% or less. The above CTFE concentration may be maintained until the end of the polymerization reaction, or depressurization may be performed during the reaction. CTFE is preferably charged all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0142] When CTFE is used as the modified monomer, it is preferable not to release the pressure in the emulsion polymerization after the CTFE is charged into the polymerization vessel until the polymerization is completed. This allows the CTFE to remain in the system until the end of the polymerization, and the breaking strength of the obtained PTFE can be further increased.

[0143] The coagulation in step (B) can be carried out by a known method.

[0144] In step (C), the wet powder obtained in step (B) is placed in a container having air permeability at the bottom and / or sides, and heat-treated for 2 hours or more at a temperature of 130 to 300° C. By carrying out heat treatment under such extremely limited conditions, the fluorine-containing compound having a molecular weight of 1000 or less can be efficiently removed together with water, and the contents of the fluorine-containing compound and water can be within the above-mentioned ranges.

[0145] The temperature of the heat treatment in step (C) is preferably 140°C or higher, more preferably 150°C or higher, even more preferably 160°C or higher, even more preferably 180°C or higher, even more preferably 200°C or higher, particularly preferably 220°C or higher, and is preferably 280°C or lower, more preferably 250°C or lower, in order to more efficiently remove moisture and fluorine-containing compounds.

[0146] The time for the heat treatment in step (C) is preferably 5 hours or more, more preferably 10 hours or more, and even more preferably 15 hours or more, in terms of more efficiently removing moisture and fluorine-containing compounds. The upper limit is not particularly limited, but is, for example, preferably 100 hours, more preferably 50 hours, and even more preferably 30 hours.

[0147] The wind speed in step (C) is preferably 0.01 m / s or more, more preferably 0.03 m / s or more, even more preferably 0.05 m / s or more, and even more preferably 0.1 m / s or more, from the viewpoint of more efficiently removing moisture and fluorine-containing compounds, and is preferably 50 m / s or less, more preferably 30 m / s or less, and even more preferably 10 m / s or less, from the viewpoint of suppressing scattering of powder.

[0148] The heat treatment in step (C) can be carried out using an electric furnace or a steam furnace. For example, it can be carried out using electric furnaces such as a parallel flow box type electric furnace, a ventilated box type electric furnace, a ventilated conveyor type electric furnace, a band electric furnace, a radiant conveyor type electric furnace, a fluidized bed electric furnace, a vacuum electric furnace, an agitation type electric furnace, an airflow type electric furnace, a hot air circulation type electric furnace, or a steam furnace corresponding to the above (a device in which the electric furnace in the device name of each electric furnace is replaced with a steam furnace). In terms of being able to remove moisture and fluorine-containing compounds more efficiently, a parallel flow box type electric furnace, a ventilated box type electric furnace, a ventilated conveyor type electric furnace, a band electric furnace, a fluidized bed electric furnace, a hot air circulation type electric furnace, or a steam furnace corresponding to the above (a device in which the electric furnace in the device name of each electric furnace is replaced with a steam furnace) is preferred.

[0149] The heat treatment in step (C) is carried out by placing the wet powder in a container with air permeability at the bottom and / or sides. The container with air permeability at the bottom and / or sides may be any container that can withstand the heat treatment temperature, and is preferably made of a metal such as stainless steel. The container having breathable bottom and / or sides is preferably a tray (bat) having breathable bottom and / or sides, and more preferably a tray having a mesh bottom and / or sides (mesh tray). The mesh is preferably either a woven mesh or a punched metal. The mesh size is preferably 2000 μm or less (ASTM standard 10 mesh or more), more preferably 595 μm or less (30 mesh or more), even more preferably 297 μm or less (50 mesh or more), even more preferably 177 μm or less (80 mesh or more), particularly preferably 149 μm or less (100 mesh or more), and particularly preferably 74 μm or less (200 mesh or more). Also, 25 μm or more (500 mesh or less) is preferable. When the mesh is a woven net, the weaving method may be, for example, plain weave, twill weave, plain tatami weave, or twill tatami weave. When the mesh is a punched metal, the aperture ratio is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more, and is preferably 95% or less.

[0150] In the step (C), the amount of the moist powder is preferably 10 g / cm from the viewpoint of more efficiently removing moisture and fluorine-containing compounds. 2 It is preferable that the thickness is less than 8 g / cm 2 More preferably, it is 5 g / cm or less. 2 More preferably, it is 3 g / cm or less. 2 It is particularly preferable that the density is 0.01 g / cm or less. 2 It is preferable that the concentration is 0.05 g / cm or more. 2 More preferably, it is 0.1 g / cm or more. 2 More preferably, it is equal to or greater than this.

[0151] The moisture content of the moist powder to be heat-treated in step (C) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, relative to the moist powder, in order to more efficiently remove moisture and fluorine-containing compounds, and is preferably 150% by mass or less, and more preferably 100% by mass or less.

[0152] The PTFE fine powder of the present disclosure has excellent physical properties that are in no way inferior to those of conventionally known PTFE fine powders, and can be used in the same manner and for the same applications as conventionally known PTFE fine powders.

[0153] The PTFE fine powder of the present disclosure is particularly useful as a raw material for an elongated body. The elongated body using the PTFE fine powder of the present disclosure is also a preferred embodiment of the present disclosure.

[0154] The above-mentioned extruded body can be obtained by extruding the PTFE fine powder of the present disclosure.

[0155] The above-mentioned stretched body is also preferably in the form of a film, a tube, a fiber, or a rod.

[0156] When the stretched body is a membrane (stretched membrane or porous membrane), it can be stretched by a known PTFE stretching method. Preferably, a sheet-like or rod-like paste extrudate is roll-stretched in the extrusion direction to obtain a uniaxially stretched film. Furthermore, a biaxially stretched film can also be obtained by stretching the film in the width direction using a tenter or the like. It is also preferable to carry out a semi-baking treatment before stretching.

[0157] The stretched body can be made into a porous body having a high porosity, and can be suitably used as a filter medium for various precision filters such as air filters and chemical filters, a support material for polymer electrolyte membranes, and the like. They are also useful as materials for products used in the fields of textiles, medicine, electrochemicals, sealing materials, air filtration, ventilation / internal pressure regulation, liquid filtration, and general consumer goods. Specific applications are given below as examples.

[0158] Electrochemical Field Dielectric material prepreg, EMI shielding material, heat transfer material, etc. More specifically, printed wiring board, electromagnetic shielding material, insulating heat transfer material, insulating material, etc. Sealing materials field Gaskets, packing, pump diaphragms, pump tubes, aircraft sealing materials, etc.

[0159] Air Filtration Field ULPA filters (for semiconductor manufacturing), HEPA filters (for hospitals and semiconductor manufacturing), cylindrical cartridge filters (for industrial use), bag filters (for industrial use), heat-resistant bag filters (for exhaust gas treatment), heat-resistant pleated filters (for exhaust gas treatment), SINBRAN filters (for industrial use), catalyst filters (for exhaust gas treatment), adsorbent filters (for HDD installation), adsorbent vent filters (for HDD installation), vent filters (for HDD installation and others), vacuum cleaner filters (for vacuum cleaners), general-purpose multi-layer felt material, GT cartridge filters (for GT compatible products), cooling filters (for electronic device housings), etc.

[0160] Ventilation / internal pressure regulation field Freeze-drying materials such as freeze-drying containers, automotive ventilation materials for electronic circuits and lamps, container applications such as container caps, protective ventilation applications for electronic devices including small terminals such as tablet terminals and mobile phones, medical ventilation applications, etc.

[0161] Liquid Filtration Semiconductor liquid filtration filters (for semiconductor manufacturing), hydrophilic PTFE filters (for semiconductor manufacturing), chemical filters (for chemical liquid treatment), pure water production line filters (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment), etc.

[0162] General consumer goods field Clothing, cable guides (movable wires for motorcycles), motorcycle clothing, cast liners (medical supporters), vacuum cleaner filters, bagpipes (musical instruments), cables (signal cables for guitars, etc.), strings (for stringed instruments), etc.

[0163] Textiles PTFE fiber (textile material), sewing thread (textile), weaving thread (textile), rope, etc.

[0164] Medical field Internal implants (extended products), artificial blood vessels, catheters, general surgery (tissue reinforcement materials), head and neck products (dura substitutes), oral health (tissue regenerative medicine), orthopedics (bandages), etc.

[0165] The PTFE fine powder of the present disclosure can also be suitably used as various additives such as dust-proof additives, drip prevention agents, and battery binders, for coating applications, and for glass cloth impregnation processing applications. In addition, the aqueous dispersion containing the PTFE fine powder of the present disclosure can be used in a variety of applications, for example, as a surface coating agent for cooking utensils, or for impregnating glass fiber, carbon fiber, Kevlar fiber, etc. to produce impregnated bodies such as roofing materials, and can also be used to form films by applying the same to an object to be coated and baking it in applications such as high-frequency printed circuit boards, conveyor belts, and packing.

[0166] The present disclosure also provides a PTFE fine powder (hereinafter also referred to as "PTFE fine powder (1a)") that is stretchable, has a standard specific gravity of 2.160 or less, and is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1000 or less. Since the PTFE fine powder (1a) is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1000 or less, problems caused by residual moisture or the fluorine-containing compounds are unlikely to occur.

[0167] The present disclosure also provides a PTFE fine powder (hereinafter also referred to as "PTFE fine powder (1b)") that is stretchable, has a standard specific gravity of 2.160 or less, and is substantially free of both moisture and the fluorine-containing compound represented by the following formula (hereinafter "PTFE fine powder (1a)" and "PTFE fine powder (1b)" are collectively referred to as "PTFE fine powder (1)"). Since the PTFE fine powder (1b) is substantially free of both moisture and the fluorine-containing compound represented by the following formula, problems caused by residual moisture or the fluorine-containing compound are unlikely to occur. F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF 2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 OCF(CF 3 )CF 2 OCF(CF 3)COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4 R is an optionally substituted imidazolium, an optionally substituted pyridinium, or an optionally substituted phosphonium. 1 is H or an organic group.

[0168] The PTFE fine powder (1) is substantially free of moisture, and therefore can be used to produce uniaxially stretched bodies having stable extrusion pressure and stretching strength, and biaxially stretched membranes having high membrane uniformity, good appearance, and stable membrane performance such as pressure loss and collection efficiency.

[0169] The PTFE fine powder (1) is extensible. The PTFE fine powder (1) being extensible means that an extensible body can be obtained in the following extensibility test. The bead obtained by the paste extrusion described below is heated at 230°C for 30 minutes to remove the lubricant from the bead. The bead (extrudate) is then cut to the appropriate length, clamped at each end with a clamp distance of 2.0 inches (51 mm) between the clamps, and heated to 300°C in an air circulating oven. The clamps are then separated at a desired speed (stretch rate) until a separation distance corresponding to the desired stretch rate (total stretch rate) is reached, and a stretch test is performed. The stretching method essentially follows the method disclosed in U.S. Pat. No. 4,576,869, except for the extrusion speed (51 cm / min instead of 84 cm / min). "Stretch rate" is the increase in length due to stretching, usually expressed in relation to the original length. In the above preparation method, the stretch rate is 100% / sec and the total stretch rate is 2400%.

[0170] The paste extrusion is carried out in the following manner. 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon Corp.) is added to 100 g of PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. The obtained PTFE fine powder mixture is then left at room temperature (25°C) for at least 1 hour before extrusion, and then paste-extruded through an orifice (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of cross-sectional area of ​​the die inlet to the cross-sectional area of ​​the die outlet) to obtain a uniform bead (beading; extrusion molded body). The extrusion speed, i.e., the ram speed, is 20 inches / min (51 cm / min).

[0171] The PTFE fine powder (1) has a standard specific gravity (SSG) of 2.160 or less. The SSG is preferably 2.150 or less, more preferably 2.145 or less, and even more preferably 2.140 or less. The SSG is also preferably equal to or greater than 2.130.

[0172] The PTFE fine powder (1) is substantially free of moisture. Substantially free of moisture means that the moisture content of the PTFE fine powder is 0.010% by mass or less. The water content is preferably 0.008% by mass or less, more preferably 0.005% by mass or less, and more preferably 0.002% by mass or less.

[0173] The PTFE fine powder (1a) is substantially free of fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially free of fluorine-containing compounds having a molecular weight of not more than 1000" means that the amount of the fluorine-containing compounds is not more than 25 ppb by mass relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0174] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include those mentioned above. The PTFE fine powder (1) is preferably obtained by polymerization carried out in the presence of a fluorine-containing surfactant.

[0175] The fluorine-containing surfactant may also be any of those mentioned above, and in particular, may be a compound represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and,

Chem.

[0176] When the PTFE fine powder (1) is substantially free of any of the fluorine-containing compounds represented by the above formulas, the occurrence of problems due to the remaining fluorine-containing compounds can be suppressed. "Substantially free of any of the fluorine-containing compounds represented by the above formulas" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0177] The PTFE fine powder (1) preferably does not substantially contain the fluorine-containing compound represented by the above general formula (2), and more preferably does not substantially contain any of the fluorine-containing compounds represented by the above general formulas (1) to (4), thereby making it possible to suppress the occurrence of problems caused by the remaining fluorine-containing compounds. "Substantially free of the fluorine-containing compound represented by the above general formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0178] It is also preferable that the PTFE fine powder (1) is substantially free of a hydrocarbon surfactant. This can prevent problems caused by the residual hydrocarbon surfactant. It is preferable that the hydrocarbon surfactant does not contain a fluorine atom. "Substantially free of hydrocarbon surfactant" means that the amount of the hydrocarbon surfactant is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the hydrocarbon surfactant is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0179] It is preferable that the PTFE fine powder (1) does not substantially contain the above-mentioned polymer (I) (excluding PTFE).

[0180] "Substantially free of polymer (I)" means that the amount of polymer (I) is 25 ppb by mass or less based on the PTFE fine powder. The amount of the polymer (I) is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0181] The PTFE fine powder (1) may have a breaking strength of 25.0 N or more and 70.0 N or less, measured using an elongated bead obtained in an elongation test at a total elongation rate of 2400% (hereinafter also referred to as "PTFE fine powder (1-1)"). The PTFE fine powder (1-1) preferably has a breaking strength of 28.0 N or more, more preferably 30.0 N or more, and preferably 60.0 N or less, more preferably 50.0 N or less. The breaking strength is a value determined by the following method. The stretched bead (produced by stretching the bead) obtained in the stretching test described below is clamped and fixed in a movable jaw having a gauge length of 5.0 cm, and a tensile test is carried out at 25°C and a speed of 300 mm / min. The strength at the time of break is measured as the breaking strength.

[0182] The above-mentioned stretching test is carried out by the following method. The bead obtained by the paste extrusion described below is heated at 230°C for 30 minutes to remove the lubricant from the bead. The bead (extrudate) is then cut to the appropriate length, clamped at each end with a clamp distance of 2.0 inches (51 mm) between the clamps, and heated to 300°C in an air circulating oven. The clamps are then separated at a desired speed (stretch rate) until a separation distance corresponding to the desired stretch rate (total stretch rate) is reached, and a stretch test is performed. The stretching method essentially follows the method disclosed in U.S. Pat. No. 4,576,869, except for the extrusion speed (51 cm / min instead of 84 cm / min). "Stretch rate" is the increase in length due to stretching, usually expressed in relation to the original length. In the above preparation method, the stretch rate is 100% / sec and the total stretch rate is 2400%.

[0183] The paste extrusion is carried out in the following manner. 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon Corp.) is added to 100 g of PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. The obtained PTFE fine powder mixture is then left at room temperature (25°C) for at least 1 hour before extrusion, and then paste-extruded through an orifice (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of cross-sectional area of ​​the die inlet to the cross-sectional area of ​​the die outlet) to obtain a uniform bead (beading; extrusion molded body). The extrusion speed, i.e., the ram speed, is 20 inches / min (51 cm / min).

[0184] The PTFE fine powder (1-1) may have an extrusion pressure at a reduction ratio (RR) of 100 of 5 MPa or more, preferably 10 MPa or more, more preferably 12 MPa or more, even more preferably 15 MPa or more, and even more preferably 17 MPa or more. In terms of improving processability, the extrusion pressure in RR100 is preferably 50 MPa or less, more preferably 40 MPa or less, even more preferably 30 MPa or less, even more preferably 25 MPa or less, even more preferably 23 MPa or less, even more preferably 21 MPa or less, and particularly preferably 20 MPa or less.

[0185] The PTFE fine powder (1) may also have a breaking strength of 10.0 N or more and less than 25.0 N, measured using an elongated bead obtained in a stretching test at a total elongation rate of 2400% (hereinafter also referred to as "PTFE fine powder (1-2)"). The PTFE fine powder (1-2) preferably has a breaking strength of 12.0 N or more, more preferably 15.0 N or more, and preferably 23.0 N or less, more preferably 20.0 N or less.

[0186] In addition, the PTFE fine powder (1-2) has an extrusion pressure of preferably 18 MPa or less, more preferably 17 MPa or less, even more preferably 16 MPa or less, even more preferably 15 MPa or less, and preferably 8 MPa or more, more preferably 10 MPa or more in RR100.

[0187] The strength ratio of the PTFE fine powder (1), expressed as breaking strength (N) / extrusion pressure (MPa), is preferably 1.85 N / MPa or more, more preferably 1.90 N / MPa or more, even more preferably more than 1.90 N / MPa, even more preferably 1.95 N / MPa or more, even more preferably 2.00 N / MPa or more, even more preferably 2.05 N / MPa or more, even more preferably 2.10 N / MPa or more, even more preferably 2.20 N / MPa or more, and particularly preferably 2.25 N / MPa or more. The higher the strength ratio, the better, but it may be 5.00 N / MPa or less, or 4.00 N / MPa or less. A higher strength ratio means a higher breaking strength and a lower extrusion pressure. The breaking strength and extrusion pressure are values ​​determined by the above-mentioned method.

[0188] In order to further improve the heat resistance, the PTFE fine powder (1) preferably has a stress relaxation time of 450 seconds or more, more preferably 500 seconds or more, even more preferably 550 seconds or more, and particularly preferably 600 seconds or more. The longer the stress relaxation time, the better, but it may be 2000 seconds or less, or may be 1000 seconds or less. The above stress relaxation time is a value determined by the following method. Both ends of the stretched bead obtained in the same manner as in the above stretch evaluation test, except that the clamp distance was 1.5 inches (38 mm) and the stretching speed was 1000% / sec, and a taut bead sample with a total length of 8 inches (20 cm) was obtained by connecting them to fixtures. The oven was kept at 390°C and the fixture was inserted into the oven through a (covered) slit in the side of the oven. The time required for the bead sample to break from the point of insertion into the oven was measured as the stress relaxation time.

[0189] Other properties of the PTFE fine powder (1) may be similar to those of the PTFE fine powder of the present disclosure described above.

[0190] The PTFE fine powder (1) preferably contains substantially no organic solvent. "Containing substantially no organic solvent" means that the content of the organic solvent in the PTFE fine powder is 5% by mass or less. The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.

[0191] The PTFE fine powder (1) (PTFE fine powders (1-1) and (1-2)) can be suitably produced by a production method including, for example, a step (A1) of preparing an aqueous dispersion of PTFE, a step (B1) of coagulating the aqueous dispersion to obtain a wet powder of PTFE, and a step (C1) of placing the wet powder in a container whose bottom and / or sides are breathable and heat-treating it at a temperature of 130 to 300°C for 2 hours or more to obtain a PTFE fine powder.

[0192] Step (A1) can be carried out in the same manner as the above-mentioned step (A). From the viewpoint of easily obtaining the PTFE fine powder (1-2), the amount added when the water-soluble radical polymerization initiator is used as the polymerization initiator is preferably an amount corresponding to 0.1 ppm or more relative to the aqueous medium, more preferably an amount corresponding to 1.0 ppm or more, even more preferably an amount corresponding to 5.0 ppm or more, even more preferably an amount corresponding to 10.0 ppm or more, and preferably an amount corresponding to 500 ppm or less, more preferably an amount corresponding to 200 ppm or less, even more preferably an amount corresponding to 100 ppm or less, and even more preferably an amount corresponding to 50 ppm or less.

[0193] Step (B1) can be carried out in the same manner as the above-mentioned step (B).

[0194] Step (C1) can be carried out in the same manner as the above-mentioned step (C). From the viewpoint of easily obtaining the PTFE fine powder (1-1), the temperature of the heat treatment in the step (C1) is preferably 150°C or higher, more preferably 160°C or higher, even more preferably 180°C or higher, and even more preferably 200°C or higher. From the viewpoint of easily obtaining the PTFE fine powder (1-2), the temperature of the heat treatment in the step (C1) is preferably 200°C or less, more preferably 180°C or less, even more preferably 160°C or less, and even more preferably 150°C or less.

[0195] The PTFE fine powder (1) has excellent physical properties that are in no way inferior to those of the conventionally known PTFE fine powders, and can be used in the same manner and for the same applications as the conventionally known PTFE fine powders.

[0196] The PTFE fine powder (1) can be suitably used for the same applications as the PTFE fine powder of the present disclosure described above, but is particularly useful as an elongated material. An elongated body using the PTFE fine powder (1) as an elongated material is also a suitable embodiment of the present disclosure.

[0197] The above-mentioned stretched body can be obtained by stretching the PTFE fine powder (1).

[0198] The above-mentioned stretched body is also preferably in the form of a film, a tube, a fiber, or a rod.

[0199] When the stretched body is a membrane (stretched membrane or porous membrane), it can be stretched by a known PTFE stretching method. Preferably, the sheet- or rod-shaped paste extrudate is rolled in the extrusion direction, dried to obtain an unsintered film, and further roll-stretched to obtain a uniaxially stretched film. Furthermore, a biaxially stretched film can also be obtained by stretching the film in the width direction using a tenter or the like. It is also preferable to carry out a semi-baking treatment before stretching.

[0200] The stretched body can be made into a porous body having a high porosity, and can be suitably used as a filter medium for various precision filters such as air filters and chemical filters, a support material for polymer electrolyte membranes, and the like. They are also useful as materials for products used in the fields of textiles, medicine, electrochemicals, sealing materials, air filtration, ventilation / internal pressure regulation, liquid filtration, and general consumer goods. Specific applications are given below as examples.

[0201] Electrochemical Field Dielectric material prepreg, EMI shielding material, heat transfer material, etc. More specifically, printed wiring board, electromagnetic shielding material, insulating heat transfer material, insulating material, etc. Sealing materials field Gaskets, packing, pump diaphragms, pump tubes, aircraft sealing materials, etc.

[0202] Air Filtration Field ULPA filters (for semiconductor manufacturing), HEPA filters (for hospitals and semiconductor manufacturing), cylindrical cartridge filters (for industrial use), bag filters (for industrial use), heat-resistant bag filters (for exhaust gas treatment), heat-resistant pleated filters (for exhaust gas treatment), SINBRAN filters (for industrial use), catalyst filters (for exhaust gas treatment), adsorbent filters (for HDD installation), adsorbent vent filters (for HDD installation), vent filters (for HDD installation and others), vacuum cleaner filters (for vacuum cleaners), general-purpose multi-layer felt material, GT cartridge filters (for GT compatible products), cooling filters (for electronic device housings), etc.

[0203] Ventilation / internal pressure regulation field Freeze-drying materials such as freeze-drying containers, automotive ventilation materials for electronic circuits and lamps, container applications such as container caps, protective ventilation applications for electronic devices including small terminals such as tablet terminals and mobile phones, medical ventilation applications, etc.

[0204] Liquid Filtration Semiconductor liquid filtration filters (for semiconductor manufacturing), hydrophilic PTFE filters (for semiconductor manufacturing), chemical filters (for chemical liquid treatment), pure water production line filters (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment), etc.

[0205] General consumer goods field Clothing, cable guides (movable wires for motorcycles), motorcycle clothing, cast liners (medical supporters), vacuum cleaner filters, bagpipes (musical instruments), cables (signal cables for guitars, etc.), strings (for stringed instruments), etc.

[0206] Textiles PTFE fiber (textile material), sewing thread (textile), weaving thread (textile), rope, etc.

[0207] Medical field Internal implants (extended products), artificial blood vessels, catheters, general surgery (tissue reinforcement materials), head and neck products (dura substitutes), oral health (tissue regenerative medicine), orthopedics (bandages), etc.

[0208] The stretched body using the PTFE fine powder (1-1) is suitably used as a porous membrane, a biaxially stretched membrane, or a filter material. The stretched product using the PTFE fine powder (1-2) is useful as a material for products used in the field of air filtration, and among them, is particularly suitable for use as a HEPA filter.

[0209] The PTFE fine powder (1) can be suitably used as a dustproof additive, an anti-drip agent, a binder for batteries, and other various additives, in coating applications, and in glass cloth impregnation processing applications. In addition, the aqueous dispersion containing the PTFE fine powder (1) can be used in various applications, for example, as a surface coating agent for cooking utensils, or for impregnating glass fiber, carbon fiber, Kevlar fiber, etc. to produce impregnated bodies such as roofing materials, and can also be used to form films by applying the same to substrates and baking them in applications such as high-frequency printed circuit boards, conveyor belts, and packing.

[0210] The present disclosure also provides a modified PTFE fine powder (hereinafter also referred to as "PTFE fine powder (2a)") which can be paste-extruded, has a standard specific gravity of 2.135 to 2.200, and is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1000 or less. Since the PTFE fine powder (2a) is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1000 or less, problems caused by residual moisture or the fluorine-containing compounds are unlikely to occur.

[0211] The present disclosure also provides a modified PTFE fine powder (hereinafter also referred to as "PTFE fine powder (2b)") which can be paste-extruded, has a standard specific gravity of 2.135 to 2.200, and is substantially free of both moisture and the fluorine-containing compound represented by the following formula (hereinafter "PTFE fine powder (2a)" and "PTFE fine powder (2b)" are collectively referred to as "PTFE fine powder (2)"). Since the PTFE fine powder (2b) is substantially free of both moisture and the fluorine-containing compound represented by the following formula, problems caused by residual moisture or the fluorine-containing compound are unlikely to occur. F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF 2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4 R is an optionally substituted imidazolium, an optionally substituted pyridinium, or an optionally substituted phosphonium. 1 is H or an organic group.

[0212] Since the PTFE fine powder (2) contains substantially no moisture, the extrusion pressure is stable, there is little fluctuation in the wire diameter, and no sparks or cracks occur, making it possible to produce molded products with good appearance.

[0213] The PTFE fine powder (2) can be paste extruded. If the RR1500 extrusion pressure exceeds 150 MPa during the measurement, it is determined that the paste cannot be extruded. In addition, if the rod-shaped material obtained by RR1500 extrusion is subjected to a tensile measurement and breaks at an elongation of 5% or less, it is determined that the paste cannot be extruded. Here, the tensile measurement means pulling the rod-shaped material at a tensile speed of 200 mm / min at room temperature. Moreover, if the extrusion pressure does not reach an equilibrium state, it is determined that extrusion is not possible. The phrase "paste extrudable" refers to a state other than that in which paste extrusion is not possible or that which is determined to be unextrudable, and refers to a state in which a uniform extrudate (rod-shaped product) can be obtained.

[0214] The extrusion pressure in RR1500 is measured by the following method. 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name Isopar G, ExxonMobil) as an extrusion aid are mixed in a glass bottle and aged for 1 hour at room temperature (25±2°C). Next, the mixture is filled into an extrusion die (with a constriction angle of 30° and an orifice (orifice diameter: 0.65 mm, orifice length: 2 mm) at the lower end) with a cylinder (inner diameter 25.4 mm), and a load of 1.2 MPa is applied to the piston inserted into the cylinder and held for 1 minute. Immediately after that, the mixture is extruded from the orifice at room temperature at a ram speed of 20 mm / min to obtain a rod-shaped product. In the latter half of the extrusion, the pressure at the part where the pressure is in equilibrium is divided by the cross-sectional area of ​​the cylinder to obtain the extrusion pressure.

[0215] The PTFE fine powder (2) is substantially free of moisture. Substantially free of moisture means that the moisture content of the PTFE fine powder is 0.010% by mass or less. The water content is preferably 0.008% by mass or less, more preferably 0.005% by mass or less, and even more preferably 0.002% by mass or less.

[0216] The PTFE fine powder (2a) is substantially free of fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially free of fluorine-containing compounds having a molecular weight of not more than 1000" means that the amount of the fluorine-containing compounds is not more than 25 ppb by mass relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0217] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include those mentioned above. The PTFE fine powder (2) is preferably obtained by polymerization carried out in the presence of a fluorine-containing surfactant.

[0218] The fluorine-containing surfactant may also be any of those mentioned above, particularly, compounds represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF 2 ) 7 COOM, F(CF 2 ) 5 COOM, H(CF 2 ) 6 COOM, H(CF 2 ) 7 COOM, CF 3 O(CF 2 ) 3 OCHFCF 2 COOM, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF3 )COOM, CF 3 CF 2 CF 2 OCF(CF 3 )COOM, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM, C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM, CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and,

Chem.

[0219] When the PTFE fine powder (2) is substantially free of any of the fluorine-containing compounds represented by the above formulas, the occurrence of problems due to the remaining fluorine-containing compounds can be suppressed. "Substantially free of any of the fluorine-containing compounds represented by the above formulas" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0220] The PTFE fine powder (2) preferably does not substantially contain the fluorine-containing compound represented by the above general formula (2), and more preferably does not substantially contain any of the fluorine-containing compounds represented by the above general formulas (1) to (4), thereby making it possible to suppress the occurrence of problems caused by the remaining fluorine-containing compounds. "Substantially free of the fluorine-containing compound represented by the above general formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0221] It is also preferable that the PTFE fine powder (2) is substantially free of a hydrocarbon surfactant. This can prevent problems caused by the residual hydrocarbon surfactant. The hydrocarbon surfactant preferably does not contain a fluorine atom. "Substantially free of hydrocarbon surfactant" means that the amount of the hydrocarbon surfactant is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the hydrocarbon surfactant is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0222] It is preferable that the PTFE fine powder (2) does not substantially contain the above-mentioned polymer (I) (excluding PTFE).

[0223] "Substantially free of polymer (I)" means that the amount of polymer (I) is 25 ppb by mass or less based on the PTFE fine powder. The amount of the polymer (I) is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0224] The PTFE fine powder (2) has a standard specific gravity (SSG) of 2.135 to 2.200. The SSG is preferably 2.190 or less, more preferably 2.185 or less, even more preferably 2.180 or less, even more preferably 2.175 or less, and is preferably 2.145 or more, more preferably 2.155 or more, even more preferably 2.160 or more, and even more preferably 2.165 or more.

[0225] The PTFE fine powder (2) is preferably extruded at a pressure of 15 to 80 MPa at RR1500. The extrusion pressure at RR1500 is more preferably 70 MPa or less, even more preferably 60 MPa or less, and even more preferably 55 MPa or less, and is more preferably 20 MPa or more, and even more preferably 25 MPa or more.

[0226] The extrusion pressure in RR1500 is measured by the following method. 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name Isopar G, ExxonMobil) as an extrusion aid are mixed in a glass bottle and aged for 1 hour at room temperature (25±2°C). Next, the mixture is filled into an extrusion die (with a constriction angle of 30° and an orifice (orifice diameter: 0.65 mm, orifice length: 2 mm) at the lower end) with a cylinder (inner diameter 25.4 mm), and a load of 1.2 MPa is applied to the piston inserted into the cylinder and held for 1 minute. Immediately after that, the mixture is extruded from the orifice at room temperature at a ram speed of 20 mm / min to obtain a rod-shaped product. In the latter half of the extrusion, the pressure at the part where the pressure is in equilibrium is divided by the cross-sectional area of ​​the cylinder to obtain the extrusion pressure.

[0227] The PTFE fine powder (2) is a modified PTFE fine powder. That is, the PTFE constituting the PTFE fine powder (2) is a modified PTFE containing a polymerization unit (TFE unit) based on tetrafluoroethylene (TFE) and a polymerization unit (hereinafter also referred to as a "modified monomer unit") based on a modified monomer. The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units.

[0228] The modified PTFE preferably has a modified monomer unit content in the range of 0.00001 to 1.0% by mass based on the total polymerized units. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, even more preferably 0.20% by mass, even more preferably 0.15% by mass, even more preferably 0.10% by mass, even more preferably 0.08% by mass, especially preferably 0.05% by mass, and most preferably 0.03% by mass.

[0229] Examples of the modifying monomer include those exemplified for the PTFE fine powder of the present disclosure described above. As the above-mentioned modified monomer, from the viewpoint of easily obtaining the above-mentioned properties, preferred are fluoro(alkyl vinyl ethers) such as perfluoro(alkyl vinyl ether) [PAVE]; vinyl heterocycles such as perfluoro-2,2-dimethyl-1,3-dioxole [PDD]; and fluoroolefins such as hexafluoropropylene [HFP] and chlorotrifluoroethylene [CTFE], and the like, and one or more of these can be used. Among them, at least one selected from the group consisting of fluoro(alkyl vinyl ether) and fluoroolefin is preferred, and at least one selected from the group consisting of PAVE, HFP and CTFE is more preferred. It is also preferred to use PAVE and HFP in combination. As PAVE, perfluoro(propyl vinyl ether) [PPVE] is preferred.

[0230] In order to further improve the paste extrudability, the modified PTFE constituting the PTFE fine powder (2) preferably has a core-shell structure. In the above-mentioned core-shell structure, the core and the shell do not necessarily have to have a clear boundary therebetween, and the modified PTFE constituting the core and the modified PTFE constituting the shell may be mixed near the boundary between the core and the shell.

[0231] The core in the above core-shell structure is preferably a modified PTFE having polymerized units based on a modified monomer. The modifying monomer in the core is preferably at least one selected from the group consisting of fluoro(alkyl vinyl ether), vinyl heterocycles and fluoroolefins, more preferably at least one selected from the group consisting of fluoro(alkyl vinyl ether) and fluoroolefins, and even more preferably at least one selected from the group consisting of PAVE, HFP and CTFE.

[0232] The shell in the above core-shell structure is preferably a modified PTFE having polymerized units based on a modifying monomer and / or a modified PTFE obtained by polymerization using a chain transfer agent. The modifying monomer in the shell is preferably at least one selected from the group consisting of fluoro(alkyl vinyl ether)s and fluoroolefins, more preferably at least one selected from the group consisting of PAVE, HFP and CTFE, and even more preferably at least one selected from the group consisting of HFP and CTFE.

[0233] The chain transfer agent is not particularly limited as long as it reduces the molecular weight of the modified PTFE constituting the shell, and examples thereof include non-peroxide organic compounds such as water-soluble alcohols, hydrocarbons and fluorinated hydrocarbons, water-soluble organic peroxides such as disuccinic acid peroxide [DSP], and persulfates such as ammonium persulfate [APS] and potassium persulfate [KPS]. The chain transfer agent may contain at least one of a non-peroxide organic compound, a water-soluble organic peroxide, and a persulfate. In the chain transfer agent, one or more of each of the non-peroxide organic compounds, the water-soluble organic peroxides and the persulfates can be used.

[0234] The chain transfer agent is preferably at least one selected from the group consisting of water-soluble alcohols having 1 to 4 carbon atoms, hydrocarbons having 1 to 4 carbon atoms, and fluorohydrocarbons having 1 to 4 carbon atoms, in that it has good dispersibility and uniformity in the reaction system, more preferably at least one selected from the group consisting of methane, ethane, n-butane, isobutane, methanol, HFC-134a, HFC-32, DSP, APS, and KPS, further preferably methanol and / or isobutane, and particularly preferably methanol.

[0235] Other properties of the PTFE fine powder (2) may be similar to those of the PTFE fine powder of the present disclosure described above.

[0236] The PTFE fine powder (2) preferably contains substantially no organic solvent. "Containing substantially no organic solvent" means that the content of the organic solvent in the PTFE fine powder is 5% by mass or less. The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.

[0237] The PTFE fine powder (2) can be suitably produced by a production method including, for example, a step (A2) of preparing an aqueous dispersion of modified PTFE, a step (B2) of coagulating the aqueous dispersion to obtain a wet powder of modified PTFE, and a step (C2) of placing the wet powder in a container whose bottom and / or sides are breathable and heat-treating it at a temperature of 130 to 300°C for 2 hours or more to obtain a PTFE fine powder.

[0238] The above step (A2) is preferably a step of emulsion polymerizing TFE and a modifying monomer. The step (A2) preferably includes a step (1) of feeding a modified monomer into a reaction system at the beginning of the polymerization reaction and carrying out the polymerization reaction, and a step (2) of introducing a chain transfer agent and / or a modified monomer into the reaction system after the step (1).

[0239] The modified monomer in step (1) may be, for example, a fluoro(alkyl vinyl ether) such as perfluoro(alkyl vinyl ether) [PAVE]; a vinyl heterocycle such as perfluoro-2,2-dimethyl-1,3-dioxole [PDD]; or a fluoroolefin such as hexafluoropropylene [HFP] or chlorotrifluoroethylene [CTFE]. One or more of these may be used. Among them, at least one selected from the group consisting of fluoro(alkyl vinyl ether)s and fluoroolefins is preferred, and at least one selected from the group consisting of PAVE, HFP, and CTFE is more preferred. It is also preferable to use PAVE and HFP in combination as the modifying monomers in step (1). A preferred PAVE is perfluoro(propyl vinyl ether) [PPVE].

[0240] The chain transfer agent in step (2) is not particularly limited as long as it reduces the molecular weight of the modified PTFE constituting the shell of the core-shell structure, and examples thereof include non-peroxide organic compounds such as water-soluble alcohols, hydrocarbons and fluorinated hydrocarbons, water-soluble organic peroxides such as disuccinic acid peroxide [DSP], and persulfates such as ammonium persulfate [APS] and potassium persulfate [KPS]. The chain transfer agent may contain at least one of a non-peroxide organic compound, a water-soluble organic peroxide, and a persulfate. In the chain transfer agent, one or more of each of the non-peroxide organic compounds, the water-soluble organic peroxides and the persulfates can be used.

[0241] The chain transfer agent is preferably at least one selected from the group consisting of water-soluble alcohols having 1 to 4 carbon atoms, hydrocarbons having 1 to 4 carbon atoms, and fluorohydrocarbons having 1 to 4 carbon atoms, in that it has good dispersibility and uniformity in the reaction system, more preferably at least one selected from the group consisting of methane, ethane, n-butane, isobutane, methanol, HFC-134a, HFC-32, DSP, APS, and KPS, further preferably methanol and / or isobutane, and particularly preferably methanol.

[0242] The modifying monomer in step (2) is preferably at least one selected from the group consisting of the above-mentioned fluoro(alkyl vinyl ether) and fluoroolefin, more preferably at least one selected from the group consisting of PAVE, HFP and CTFE, and even more preferably at least one selected from the group consisting of HFP and CTFE.

[0243] In the step (2), it is also preferable to use the chain transfer agent and the modifying monomer in combination.

[0244] When CTFE is used as the modifying monomer in step (1), it is preferable to use CTFE as the modifying monomer in step (2). When PAVE (and HFP) are used as the modifying monomer in step (1), it is preferable to use methanol (and HFP as the modifying monomer) as the chain transfer agent in step (2).

[0245] In the above step (1), it is preferable to carry out the polymerization reaction until the conversion rate of TFE used in the entire emulsion polymerization process including steps (1) and (2) reaches 80% or more, preferably 80 to 97%, and more preferably 85 to 95%. In this specification, the above-mentioned "conversion rate" refers to the proportion of the amount of TFE consumed in the polymerization from the start of polymerization to a certain point during the polymerization, relative to the amount of TFE corresponding to the target amount of TFE units.

[0246] In the above steps (1) and (2), the reaction conditions can be appropriately set depending on the type of modifying agent used, the desired composition and yield of the modified PTFE, and the like.

[0247] The emulsion polymerization can be carried out in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator. If necessary, a dispersion stabilizer or the like may be used. The anionic fluorine-containing surfactant can be present in an amount of 0.02 to 0.3% by mass of the aqueous medium.

[0248] As the polymerization initiator, for example, persulfates such as ammonium persulfate [APS], water-soluble organic peroxides such as disuccinic acid peroxide [DSP], etc. can be used, and these polymerization initiators can be used alone or in combination of two or more. Among them, APS, DSP, etc. are preferred because they also act as the above-mentioned chain transfer agent. The emulsion polymerization is preferably carried out in an amount of 0.0001 to 0.02 parts by mass of the polymerization initiator per 100 parts by mass of the aqueous medium.

[0249] As the aqueous medium, the same one as in the above-mentioned step (A) can be used.

[0250] The emulsion polymerization can be carried out at a polymerization temperature of 10 to 95°C, but is preferably carried out at a temperature of 60 to 90°C when a persulfate or a water-soluble organic peroxide is used as the polymerization initiator. The above emulsion polymerization can be carried out usually at a pressure of 0.5 to 3.9 MPaG, preferably 0.6 to 3 MPaG. The emulsion polymerization can also be carried out by carrying out the reaction at a pressure of 0.5 MPaG or less in the early stage of the polymerization, particularly until the TFE conversion rate reaches 15% or less of the total, and then maintaining the pressure at a level exceeding 0.5 MPaG; alternatively, the reaction pressure can be reduced to, for example, 0.1 MPaG or less during the formation of the core, and TFE is again supplied to carry out the reaction at a predetermined pressure.

[0251] Step (B2) can be carried out in the same manner as the above-mentioned step (B).

[0252] Step (C2) can be carried out in the same manner as the above-mentioned step (C). In order to obtain a PTFE fine powder having even better paste extrudability, the temperature of the heat treatment in step (C2) is preferably 200°C or lower, more preferably 170°C or lower, and even more preferably 150°C or lower.

[0253] The PTFE fine powder (2) has excellent physical properties that are in no way inferior to those of the conventionally known PTFE fine powders, and can be used in the same manner and for the same applications as the conventionally known PTFE fine powders.

[0254] The PTFE fine powder (2) is particularly useful as a raw material for a molded article. A molded article using the PTFE fine powder (2) is also a preferred embodiment of the present disclosure.

[0255] The above molded product can be obtained by molding the PTFE fine powder (2).

[0256] The molding is not particularly limited, but is usually carried out by paste extrusion. The above paste extrusion can be carried out by setting appropriate conditions depending on the desired shape, application, etc. of the molded product. For example, it can be carried out by mixing an extrusion aid, maturing for about 1 to 24 hours, preforming at a pressure of 0.5 to 5.0 MPa, extruding at an extrusion pressure of 2 to 100 MPa, and firing at 360 to 460°C.

[0257] The above-mentioned molded article can be suitably used as a printed circuit board, an electric wire coating, a tube, etc., which require heat resistance and chemical resistance, for example, in aircraft, automobiles, medical equipment, precision machinery, etc., and in particular, it is preferably used as an electric wire coating material, which requires core wire adhesion strength, etc., or a tube such as a medical tube.

[0258] The present disclosure also provides a modified polytetrafluoroethylene fine powder (hereinafter also referred to as "PTFE fine powder (3)") modified with perfluorovinyl ether, which can be paste-extruded, has a standard specific gravity of 2.135 to 2.200, and is substantially free of both moisture and the fluorine-containing compound represented by general formula (2). General formula (2):[C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14; M + represents a cation.)

[0259] Since the PTFE fine powder (3) contains substantially no moisture, the extrusion pressure is stable, there is little fluctuation in the wire diameter, and no sparks or cracks occur, making it possible to produce molded products with good appearance.

[0260] The PTFE fine powder (3) is paste extrudable. If the RR1500 extrusion pressure exceeds 150 MPa during the measurement, it is determined that the paste cannot be extruded. In addition, if the rod-shaped material obtained by RR1500 extrusion is subjected to a tensile measurement and breaks at an elongation of 5% or less, it is determined that the paste cannot be extruded. Here, the tensile measurement means pulling the rod-shaped material at a tensile speed of 200 mm / min at room temperature. Moreover, if the extrusion pressure does not reach an equilibrium state, it is determined that extrusion is not possible. The phrase "paste extrudable" refers to a state other than that in which paste extrusion is not possible or that which is determined to be unextrudable, and refers to a state in which a uniform extrudate (rod-shaped product) can be obtained.

[0261] The extrusion pressure in RR1500 is measured by the following method. 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name Isopar G, ExxonMobil) as an extrusion aid are mixed in a glass bottle and aged for 1 hour at room temperature (25±2°C). Next, the mixture is filled into an extrusion die (with a constriction angle of 30° and an orifice (orifice diameter: 0.65 mm, orifice length: 2 mm) at the lower end) with a cylinder (inner diameter 25.4 mm), and a load of 1.2 MPa is applied to the piston inserted into the cylinder and held for 1 minute. Immediately after that, the mixture is extruded from the orifice at room temperature at a ram speed of 20 mm / min to obtain a rod-shaped product. In the latter half of the extrusion, the pressure at the part where the pressure is in equilibrium is divided by the cross-sectional area of ​​the cylinder to obtain the extrusion pressure.

[0262] The PTFE fine powder (3) is substantially free of moisture. Substantially free of moisture means that the moisture content of the PTFE fine powder is 0.010% by mass or less. The water content is preferably 0.008% by mass or less, more preferably 0.005% by mass or less, and even more preferably 0.002% by mass or less.

[0263] The PTFE fine powder (3) does not substantially contain a fluorine-containing compound represented by the following general formula (2). General formula (2):[C n-1F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14; M + represents a cation.) This makes it possible to suppress the occurrence of problems caused by the remaining fluorine-containing compound. "Substantially free of the fluorine-containing compound represented by the general formula (2)" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0264] Examples of the fluorine-containing compound represented by the general formula (2) include those mentioned above.

[0265] It is more preferable that the PTFE fine powder (3) does not substantially contain any of the fluorine-containing compounds represented by the above general formulas (1), (3) and (4), thereby making it possible to suppress the occurrence of problems caused by the remaining fluorine-containing compounds. "Substantially free of the fluorine-containing compound represented by the above general formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0266] The PTFE fine powder (3) preferably does not substantially contain fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially does not contain fluorine-containing compounds having a molecular weight of not more than 1000" means that the amount of the fluorine-containing compounds is not more than 25 ppb by mass relative to the PTFE fine powder. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0267] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include those mentioned above. The PTFE fine powder (3) is preferably obtained by polymerization in the presence of a fluorine-containing surfactant. Examples of the fluorine-containing surfactant include those mentioned above.

[0268] It is also preferable that the PTFE fine powder (3) is substantially free of a hydrocarbon surfactant. This can prevent problems caused by the residual hydrocarbon surfactant. It is preferable that the hydrocarbon surfactant does not contain a fluorine atom. "Substantially free of hydrocarbon surfactant" means that the amount of the hydrocarbon surfactant is 25 ppb by mass or less relative to the PTFE fine powder. The amount of the hydrocarbon surfactant is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0269] It is preferable that the PTFE fine powder (3) does not substantially contain the above-mentioned polymer (I) (excluding PTFE).

[0270] "Substantially free of polymer (I)" means that the amount of polymer (I) is 25 ppb by mass or less based on the PTFE fine powder. The amount of the polymer (I) is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, particularly preferably 3 mass ppb or less, and even more preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0271] The PTFE fine powder (3) has a standard specific gravity (SSG) of 2.135 to 2.200. The SSG is preferably 2.190 or less, more preferably 2.185 or less, even more preferably 2.180 or less, even more preferably 2.175 or less, and is preferably 2.145 or more, more preferably 2.155 or more, even more preferably 2.160 or more, and even more preferably 2.165 or more.

[0272] The PTFE fine powder (3) is preferably extruded at a pressure of 15 to 80 MPa in RR1500. The extrusion pressure in RR1500 is more preferably 70 MPa or less, even more preferably 60 MPa or less, and even more preferably 55 MPa or less, and is more preferably 20 MPa or more, and even more preferably 25 MPa or more.

[0273] The extrusion pressure in RR1500 is measured by the following method. 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name Isopar G, ExxonMobil) as an extrusion aid are mixed in a glass bottle and aged for 1 hour at room temperature (25±2°C). Next, the mixture is filled into an extrusion die (with a constriction angle of 30° and an orifice (orifice diameter: 0.65 mm, orifice length: 2 mm) at the lower end) with a cylinder (inner diameter 25.4 mm), and a load of 1.2 MPa is applied to the piston inserted into the cylinder and held for 1 minute. Immediately after that, the mixture is extruded from the orifice at room temperature at a ram speed of 20 mm / min to obtain a rod-shaped product. In the latter half of the extrusion, the pressure at the part where the pressure is in equilibrium is divided by the cross-sectional area of ​​the cylinder to obtain the extrusion pressure.

[0274] The PTFE fine powder (3) is a modified PTFE fine powder modified with perfluorovinyl ether. That is, the PTFE constituting the PTFE fine powder (3) is a modified PTFE containing a polymerization unit (TFE unit) based on tetrafluoroethylene (TFE) and a polymerization unit (hereinafter also referred to as "perfluorovinyl ether unit") based on perfluorovinyl ether. The modified PTFE may contain 99.0 mass% or more of TFE units and 1.0 mass% or less of perfluorovinyl ether units. The modified PTFE may be composed only of TFE units and perfluorovinyl ether units.

[0275] The modified PTFE preferably has a perfluorovinyl ether unit content of 0.02% by mass or more and 0.30% by mass or less based on the total polymerized units. The lower limit of the perfluorovinyl ether unit content is more preferably 0.03% by mass, further preferably 0.05% by mass, and further more preferably 0.10% by mass. The upper limit of the perfluorovinyl ether unit content is preferably 0.27% by mass, and more preferably 0.25% by mass.

[0276] The above-mentioned perfluorovinyl ether may be exemplified as the PTFE fine powder of the present disclosure. The above-mentioned perfluorovinyl ether is preferably PAVE. The PAVE is preferably perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, or perfluoro(propyl vinyl ether) [PPVE], and more preferably PPVE.

[0277] The PTFE fine powder (3) may contain polymerization units based on other modified monomers other than perfluorovinyl ether (hereinafter also referred to as "other modified monomer units"). When the other modified monomer units are contained, the total amount of the perfluorovinyl ether units and the other modified monomer units is preferably 1.0% by weight or less based on the total polymerization units.

[0278] Examples of the other modifying monomer include those exemplified for the PTFE fine powder of the present disclosure described above. As the other modifying monomer, vinyl heterocycles such as perfluoro-2,2-dimethyl-1,3-dioxole [PDD]; fluoroolefins such as hexafluoropropylene [HFP] and chlorotrifluoroethylene [CTFE] are preferred, in that the above-mentioned properties can be easily obtained, and one or more of these can be used. Among these, at least one selected from the group consisting of fluoroolefins is preferred, at least one selected from the group consisting of HFP and CTFE is more preferred, and HFP is more preferred.

[0279] In order to further improve the paste extrudability, the modified PTFE constituting the PTFE fine powder (3) preferably has a core-shell structure. In the above-mentioned core-shell structure, the core and the shell do not necessarily have to have a clear boundary therebetween, and the modified PTFE constituting the core and the modified PTFE constituting the shell may be mixed near the boundary between the core and the shell.

[0280] The core in the above core-shell structure is preferably a modified PTFE having polymerization units based on perfluorovinyl ether, or a modified PTFE having polymerization units based on perfluorovinyl ether and polymerization units based on other modifying monomers. The other modifying monomer in the core is preferably at least one selected from the group consisting of vinyl heterocycles and fluoroolefins, more preferably at least one selected from the group consisting of fluoroolefins, even more preferably at least one selected from the group consisting of HFP and CTFE, and even more preferably HFP.

[0281] The shell in the above core-shell structure is preferably a modified PTFE having polymerized units based on another modifying monomer and / or a modified PTFE obtained by polymerization using a chain transfer agent. The other modifying monomer in the shell is preferably at least one selected from the group consisting of fluoroolefins, more preferably at least one selected from the group consisting of HFP and CTFE, and even more preferably HFP.

[0282] The chain transfer agent is not particularly limited as long as it reduces the molecular weight of the modified PTFE constituting the shell, and examples thereof include non-peroxide organic compounds such as water-soluble alcohols, hydrocarbons and fluorinated hydrocarbons, water-soluble organic peroxides such as disuccinic acid peroxide [DSP], and persulfates such as ammonium persulfate [APS] and potassium persulfate [KPS]. The chain transfer agent may contain at least one of a non-peroxide organic compound, a water-soluble organic peroxide, and a persulfate. In the chain transfer agent, one or more of each of the non-peroxide organic compounds, the water-soluble organic peroxides and the persulfates can be used.

[0283] The chain transfer agent is preferably at least one selected from the group consisting of water-soluble alcohols having 1 to 4 carbon atoms, hydrocarbons having 1 to 4 carbon atoms, and fluorohydrocarbons having 1 to 4 carbon atoms, in that it has good dispersibility and uniformity in the reaction system, more preferably at least one selected from the group consisting of methane, ethane, n-butane, isobutane, methanol, HFC-134a, HFC-32, DSP, APS, and KPS, further preferably methanol and / or isobutane, and particularly preferably methanol.

[0284] Other properties of the PTFE fine powder (3) may be similar to those of the PTFE fine powder of the present disclosure described above.

[0285] The PTFE fine powder (3) preferably contains substantially no organic solvent. "Containing substantially no organic solvent" means that the content of the organic solvent in the PTFE fine powder is 5% by mass or less. The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.

[0286] The PTFE fine powder (3) can be suitably produced by a production method including, for example, a step (A3) of preparing an aqueous dispersion of modified PTFE, a step (B3) of coagulating the aqueous dispersion to obtain a wet powder of modified PTFE, and a step (C3) of placing the wet powder in a container whose bottom and / or sides are breathable, and heat-treating it at a temperature of 130 to 300°C for 2 hours or more to obtain a PTFE fine powder.

[0287] The above step (A3) is preferably a step of emulsion polymerizing TFE and a perfluorovinyl ether. The step (A3) preferably includes a step (3) of feeding a perfluorovinyl ether to the reaction system at the beginning of the polymerization reaction and carrying out the polymerization reaction, and a step (4) of introducing a chain transfer agent and / or a perfluorovinyl ether into the reaction system after the step (3). In the steps (3) and (4), in addition to the perfluorovinyl ether, a modified monomer other than the perfluorovinyl ether may be added.

[0288] The perfluorovinyl ether in step (3) is preferably PAVE. Preferred PAVEs are perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, and PPVE, and more preferably PPVE.

[0289] Other modifying monomers in step (3) include vinyl heterocycles such as perfluoro-2,2-dimethyl-1,3-dioxole [PDD]; fluoroolefins such as hexafluoropropylene [HFP] and chlorotrifluoroethylene [CTFE]; and the like. One or more of these may be used. Among these, at least one selected from the group consisting of fluoroolefins is preferred, at least one selected from the group consisting of HFP and CTFE is more preferred, and HFP is even more preferred.

[0290] The chain transfer agent in step (4) is not particularly limited as long as it reduces the molecular weight of the modified PTFE constituting the shell of the core-shell structure, and examples thereof include non-peroxide organic compounds such as water-soluble alcohols, hydrocarbons and fluorinated hydrocarbons, water-soluble organic peroxides such as disuccinic acid peroxide [DSP], and persulfates such as ammonium persulfate [APS] and potassium persulfate [KPS]. The chain transfer agent may contain at least one of a non-peroxide organic compound, a water-soluble organic peroxide, and a persulfate. In the chain transfer agent, one or more of each of the non-peroxide organic compounds, the water-soluble organic peroxides and the persulfates can be used.

[0291] The chain transfer agent is preferably at least one selected from the group consisting of water-soluble alcohols having 1 to 4 carbon atoms, hydrocarbons having 1 to 4 carbon atoms, and fluorohydrocarbons having 1 to 4 carbon atoms, in that it has good dispersibility and uniformity in the reaction system, more preferably at least one selected from the group consisting of methane, ethane, n-butane, isobutane, methanol, HFC-134a, HFC-32, DSP, APS, and KPS, further preferably methanol and / or isobutane, and particularly preferably methanol.

[0292] The other modifying monomer in step (4) is preferably at least one selected from the group consisting of the above-mentioned fluoroolefins, more preferably at least one selected from the group consisting of HFP and CTFE, and even more preferably HFP.

[0293] In the step (4), it is also preferable to use the chain transfer agent in combination with the other modifying monomer.

[0294] When CTFE is used as the other modifying monomer in step (3), it is preferable to use CTFE as the other modifying monomer in step (4). When HFP is used as the other modifying monomer in step (3), it is preferable to use methanol (and HFP as the other modifying monomer) as a chain transfer agent in step (4).

[0295] In the above step (3), it is preferable to carry out the polymerization reaction until the conversion rate of TFE used in the entire emulsion polymerization process including steps (3) and (4) reaches 80% or more, preferably 80 to 97%, and more preferably 85 to 95%. In this specification, the above-mentioned "conversion rate" refers to the proportion of the amount of TFE consumed in the polymerization from the start of polymerization to a certain point during the polymerization, relative to the amount of TFE corresponding to the target amount of TFE units.

[0296] In the above steps (3) and (4), the reaction conditions can be appropriately set depending on the type of modifying agent used, the desired composition and yield of the modified PTFE, and the like.

[0297] The emulsion polymerization can be carried out in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator. If necessary, a dispersion stabilizer or the like may be used. The anionic fluorine-containing surfactant can be present in an amount of 0.02 to 0.3% by mass of the aqueous medium.

[0298] As the polymerization initiator, for example, persulfates such as ammonium persulfate [APS], water-soluble organic peroxides such as disuccinic acid peroxide [DSP], etc. can be used, and these polymerization initiators can be used alone or in combination of two or more. Among them, APS, DSP, etc. are preferred because they also act as the above-mentioned chain transfer agent. The emulsion polymerization is preferably carried out in an amount of 0.0001 to 0.02 parts by mass of the polymerization initiator per 100 parts by mass of the aqueous medium.

[0299] As the aqueous medium, the same one as in the above-mentioned step (A) can be used.

[0300] The emulsion polymerization can be carried out at a polymerization temperature of 10 to 95°C, but is preferably carried out at a temperature of 60 to 90°C when a persulfate or a water-soluble organic peroxide is used as the polymerization initiator. The above emulsion polymerization can be carried out usually at a pressure of 0.5 to 3.9 MPaG, preferably 0.6 to 3 MPaG. The emulsion polymerization can also be carried out by carrying out the reaction at a pressure of 0.5 MPaG or less in the early stage of the polymerization, particularly until the TFE conversion rate reaches 15% or less of the total, and then maintaining the pressure at a level exceeding 0.5 MPaG; alternatively, the reaction pressure can be reduced to, for example, 0.1 MPaG or less during the formation of the core, and TFE is again supplied to carry out the reaction at a predetermined pressure.

[0301] Step (B3) can be carried out in the same manner as in the above-mentioned step (B).

[0302] Step (C3) can be carried out in the same manner as in the above-mentioned step (C). In order to obtain a PTFE fine powder having even better paste extrudability, the temperature of the heat treatment in step (C3) is preferably 200°C or lower, more preferably 170°C or lower, and even more preferably 150°C or lower.

[0303] The PTFE fine powder (3) has excellent physical properties that are in no way inferior to those of the conventionally known PTFE fine powders, and can be used in the same manner and for the same applications as the conventionally known PTFE fine powders.

[0304] The PTFE fine powder (3) is particularly useful as a raw material for a molded article. A molded article using the PTFE fine powder (3) is also a preferred embodiment of the present disclosure.

[0305] The above molded product can be obtained by molding the PTFE fine powder (3).

[0306] The molding is not particularly limited, but is usually carried out by paste extrusion. The above paste extrusion can be carried out by setting appropriate conditions depending on the desired shape, application, etc. of the molded product. For example, it can be carried out by mixing an extrusion aid, maturing for about 1 to 24 hours, preforming at a pressure of 0.5 to 5.0 MPa, extruding at an extrusion pressure of 2 to 100 MPa, and firing at 360 to 460°C.

[0307] The above-mentioned molded article can be suitably used as a printed circuit board, an electric wire coating, a tube, etc., which require heat resistance and chemical resistance, for example, in aircraft, automobiles, medical equipment, precision machinery, etc., and in particular, it is preferably used as an electric wire coating material, which requires core wire adhesion strength, etc., or a tube such as a medical tube. EXAMPLES

[0308] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.

[0309] Various physical properties were measured by the following methods.

[0310] Average primary particle size The PTFE aqueous dispersion is diluted with water until the solid content is 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph are measured to create a calibration curve. Using this calibration curve, the number-average particle diameter is determined from the measured transmittance of the 550 nm projected light of each sample, and is taken as the average primary particle diameter.

[0311] apparent density Measurements were performed in accordance with JIS K6892.

[0312] Average secondary particle size Measurements were performed in accordance with JIS K6891.

[0313] Standard specific gravity (SSG) The measurements were made using samples formed in accordance with ASTM D 4895 and by the water displacement method in accordance with ASTM D 792.

[0314] Modified Monomer Content The PMVE content was determined by melting PTFE powder at 370℃. 19 F-NMR measurement was performed, and the values ​​were calculated based on the following formula from the signals derived from the functional groups obtained. PMVE content (mass%)=(664B / (300A+364B))×100 (A: CF appears around -120 ppm 2 A: Total integral of the PMVE-derived CF signal at -136 ppm and the PMVE-derived CF signal at -54 ppm. B: Total integral of the PMVE-derived CF signal at -136 ppm and the PMVE-derived CF signal at -54 ppm. 3 (integral value of the signal) The chemical shift value is the CF 2The signal peak top was set at -120 ppm. The VDF content was determined by the following method. 19 F-NMR was measured. In addition, a thin film disk was produced by pressing the PTFE powder, and the infrared absorbance measured by FT-IR was 1429 cm -1 / 2360cm -1 The absorbance ratio was calculated. 19 A calibration curve was prepared from the F-NMR measurements and the above absorbance ratios, and the VDF content was calculated from this calibration curve. The HFP content was determined by press-molding PTFE powder to create a thin-film disk, and the infrared absorbance of the thin-film disk was measured by FT-IR. -1 Absorbance at / 935cm -1 The absorbance ratio was calculated by multiplying the absorbance ratio at The CTFE content was determined by press-molding PTFE powder to create a thin film disk, measuring the infrared absorbance of the thin film disk by FT-IR, and determining the CTFE content at 957 cm -1 Absorbance / 2360cm -1 The absorbance ratio was multiplied by 0.58.

[0315] moisture content About 20 g of PTFE powder was heated at 150° C. for 2 hours, the mass was measured before and after, and the mass was calculated according to the following formula. A sample was taken three times, and the mass was calculated for each time, and the average value was calculated. Moisture content (mass%) = [(mass (g) of PTFE powder before heating) - (mass (g) of PTFE powder after heating)] / (mass (g) of PTFE powder before heating) x 100

[0316] Fluorine-containing compound content (1) 1 g of PTFE powder was weighed respectively, 10 g (12.6 ml) of methanol was added, and ultrasonic treatment was performed for 60 minutes to obtain an extract. The obtained extract was measured by LC / MS / MS. For the fluorine-containing compounds in the extract, measurement was performed using a liquid chromatograph mass spectrometer (Waters, LC-MS ACQUITY UPLC / TQD). The measurement instrument configuration and LC-MS measurement conditions are shown in Table 1. An aqueous solution of a fluorine-containing compound with a known concentration was used to prepare an aqueous solution with a content of 5 levels or more, and LC / MS analysis was performed on the aqueous solution of each content. The relationship between the content and the area of the peak corresponding to the content was plotted to draw a calibration curve. Using the above calibration curve, the area of the LC / MS chromatogram of the fluorine-containing compound in the extract was converted into the content of the fluorine-containing compound. Note that the detection limit in this measurement method is 10 mass ppb.

[0317]

Table 1

[0318] Fluorine-containing compound content (2) The content of the fluorine-containing compound contained in the PTFE powder was determined as the content of the fluorine-containing compound extracted from the powder.

[0319] <Extraction of fluorine-containing compound content from PTFE powder> 10 g (12.6 mL) of methanol was added to 1 g of PTFE powder, and ultrasonic treatment was performed at 60 °C for 2 hours. After standing at room temperature, the solid content was removed to obtain an extract.

[0320] <Measurement of perfluoroether carboxylic acids A and C> 1. Calibration curve of perfluoroether carboxylic acids A and C Five levels of methanol standard solutions of perfluoroether carboxylic acids A and C with known concentrations were prepared and measured using a liquid chromatograph mass spectrometer (Agilent, Ultivo triple quadrupole LC-MS). In each concentration range, a calibration curve was created using linear approximation from the methanol standard solution concentration and the integrated value of the peak.

[0321] Measurement equipment configuration and LC-MS measurement conditions [Table 2]

[0322] MRM measurement parameters [Table 3]

[0323] 2. Content of perfluoroether carboxylic acids A and C in PTFE powder The contents of perfluoroether carboxylic acids A and C contained in the extract were measured from a calibration curve using a liquid chromatograph mass spectrometer. The content of perfluoroether carboxylic acid A contained in the PTFE powder was calculated from the following relational formula (1). Y A =X A ×12.6 (1) Y A : Content of perfluoroether carboxylic acid A in the powder (mass ppb) X A : Content of perfluorocarboxylic acid A in the extract (ng / mL) The content of perfluoroether carboxylic acid C in the PTFE powder was calculated according to the following relational formula (2). Y C =X C ×12.6 (2) Y C : Content of perfluoroether carboxylic acid C contained in the powder (mass ppb) X C : Perfluorocarboxylic acid C content in the extract (ng / mL) The lower limit of quantification for the contents of perfluoroether carboxylic acids A and C contained in the PTFE powder is 1 ppb by mass.

[0324] <Content of compound represented by general formula (2)> The content of the compound represented by the general formula (2) was determined using a calibration curve of a linear perfluorocarboxylic acid having the same carbon number.

[0325] 1. Calibration curve of perfluorocarboxylic acid Five levels of methanol standard solutions of known concentrations of perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, and perfluorotetradecanoic acid were prepared and measured using a liquid chromatograph mass spectrometer (Agilent, Ultivo Triple Quadrupole LC-MS). A calibration curve was created using a first-order approximation from the methanol standard solution concentration and the peak integral value in each concentration range.

[0326] Measurement equipment configuration and LC-MS measurement conditions [Table 4]

[0327] MRM measurement parameters [Table 5]

[0328] 2. Content of the compound represented by general formula (2) contained in the powder The content of the compound represented by general formula (2) and having carbon number n in the extract was measured from a calibration curve using a liquid chromatograph mass spectrometer. The content of the compound represented by general formula (2) and having carbon number n in the powder was calculated using the following relational formula (3). Yn = Xn × 12.6 (3) Yn: Content (mass ppb) of the compound represented by general formula (2) with carbon number n contained in the powder Xn: Content of the compound represented by general formula (2) with carbon number n contained in the extract (ng / mL) The lower limit of quantification for the content of the compound represented by general formula (2) having n carbon atoms contained in the powder is 1 ppb by mass.

[0329] MRM measurement parameters [Table 6]

[0330] Extrusion pressure at reduction ratio 100 (RR100 extrusion pressure) 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon Corp.) was added to 100 g of PTFE powder and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. The obtained PTFE fine powder mixture was then left at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded at room temperature through an orifice (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at a reduction ratio of 100:1 (ratio of cross-sectional area of ​​the inlet and outlet of the die) to obtain a uniform bead (beading; extrusion molded body). The extrusion speed, i.e., the ram speed, was 20 inches / min (51 cm / min). The extrusion pressure was determined by measuring the load when the extrusion load reached equilibrium in the paste extrusion and dividing it by the cross-sectional area of ​​the cylinder used for paste extrusion.

[0331] Extrusion pressure at reduction ratio 1500 (RR1500 extrusion pressure) 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name Isopar G, manufactured by ExxonMobil Corporation) as an extrusion aid were mixed in a glass bottle and aged for 1 hour at room temperature (25±2°C). Next, the mixture was filled into an extrusion die (with a constriction angle of 30° and an orifice (orifice diameter: 0.65 mm, orifice length: 2 mm) at the lower end) with a cylinder (inner diameter 25.4 mm), and a load of 1.2 MPa was applied to the piston inserted into the cylinder and held for 1 minute. Immediately after that, the mixture was extruded from the orifice at room temperature at a ram speed of 20 mm / min to obtain a rod-shaped product. In the latter half of the extrusion, the pressure at the part where the pressure was in equilibrium was divided by the cross-sectional area of ​​the cylinder to obtain the extrusion pressure. If the pressure did not reach an equilibrium state, extrusion was deemed impossible.

[0332] Extrusion pressure variation coefficient In the measurement of the extrusion pressure, the load when the extrusion load of the paste extrusion reached an equilibrium state was measured, and the coefficient of variation of the extrusion pressure was calculated from the average value and standard deviation of the load in the equilibrium state. (Variation coefficient of extrusion pressure) = (Standard deviation of load) / (Average load)

[0333] Extension test The bead obtained by the above paste extrusion was heated at 230°C for 30 minutes to remove the lubricant from the bead. The bead (extrudate) was then cut to the appropriate length, clamped at each end with a clamp distance of 2.0 inches (51 mm) apart, and heated to 300°C in an air circulating oven. The clamps were then separated at a desired speed (stretch rate) until a separation distance corresponding to the desired stretch rate (total stretch rate) was achieved, and stretching tests were performed. The stretching method essentially follows the method disclosed in U.S. Pat. No. 4,576,869, except for the extrusion speed (51 cm / min instead of 84 cm / min). "Stretch rate" is the increase in length due to stretching, usually expressed in relation to the original length. In the above preparation method, the stretch rate is 100% / sec, and the total stretch rate is 2400%.

[0334] Breaking strength (measured using stretched beads obtained in a stretching test with a total stretch rate of 2400%) The stretched bead (produced by stretching the bead) obtained in the above stretching test was clamped and fixed in a movable jaw having a gauge length of 5.0 cm, and a tensile test was performed at 25°C and a speed of 300 mm / min, and the strength at the time of break was measured as the breaking strength.

[0335] Stretched film evaluation (Preparation of biaxially stretched membrane and filter medium) 100 parts by mass of PTFE powder was mixed with 28 parts by mass of hydrocarbon oil (Idemitsu Kosan's "IP Solvent 2028") as an extrusion aid. The mixture was placed in a paste extrusion device equipped with a sheet die having a rectangular extrusion port with a short side length of 2 mm and a long side length of 150 mm at the tip of the paste extrusion device, and a sheet-shaped molded body was obtained by paste extrusion. The sheet-shaped molded body was then formed into a film using a calendar roll heated to 70°C, and an unsintered film containing the aid was obtained. Next, the unsintered film containing the auxiliary was passed through a hot air drying oven at 250°C to evaporate and remove the extrusion auxiliary, and an unsintered film with an average thickness of 200 μm was obtained. This unsintered film was stretched in the longitudinal direction at a stretch ratio of 10 times to obtain a uniaxially stretched film. The stretching temperature was 250°C. Next, the obtained uniaxially stretched film (longitudinal stretched film) was stretched in the width direction at a stretch ratio of 43 times using a tenter capable of continuous clipping, to obtain a biaxially stretched film. The obtained biaxially stretched film was heat-set to obtain a PTFE porous film. The stretching temperature at this time was 290°C, the heat-setting temperature was 345°C, and the stretching speed was 330% / sec. Next, a spunbond nonwoven fabric ("Elves T0303WDO" manufactured by Unitika Ltd.) consisting of fibers with a core / sheath structure using PET as the core and PE as the sheath was used as the breathable support material, and the nonwoven fabric was laminated by heat fusion using a laminating device so as to sandwich the obtained multilayer porous membrane, thereby obtaining a three-layer filter medium.

[0336] (Extrusion pressure during molding) The extrusion pressure was measured from the paste extrusion device when the paste was extruded in the production of the biaxially stretched film. The extrusion pressure was determined by measuring the load when the extrusion load reached equilibrium during paste extrusion and dividing the load by the cross-sectional area of ​​the cylinder used for the paste extrusion.

[0337] (Appearance of unbaked film) Unbaked films with tears or holes were rated as "Bad," while homogeneous films were rated as "Good." In addition, even if the film was homogeneous, unbaked films containing additives before drying were rated as "No Good" if they had one spot of devitrification (a phenomenon in which the concentration of additives is non-uniform) per 10 m.

[0338] (Appearance of PTFE porous membrane) The appearance of the PTFE porous membrane obtained by the above-mentioned biaxially stretched membrane production was visually observed. PTFE porous membrane with one or more thin layers measuring 100 x 100 mm or more per 100 m was rated as "No Good," membrane with one or more membrane ruptures or one or more through holes per 100 m was rated as "Bad," and a homogeneous membrane was rated as "Good."

[0339] (Film thickness) Using a thickness meter (1D-110MH type, manufactured by Mitutoyo Corporation), five porous membranes were stacked and the total thickness was measured, and the measured value was divided by 5 to obtain the thickness of one porous membrane. This thickness is the thickness (average thickness) of one entire porous membrane.

[0340] Filter media evaluation (Pressure loss) A 5m section including the tip was pulled out from a long filter material wound in a roll, and the filter material was divided into 25 pieces every 200mm in the longitudinal direction and into 4 pieces every 130mm in the width direction excluding both ends, and the pressure loss was measured at 100 lattice-like locations. The pressure loss measurement here was performed by moving the filter material in the longitudinal direction using a measuring device equipped with 5 or more filter holders in the width direction of the filter material, and continuously measuring multiple lattice-like locations. The obtained measurement sample of the filter medium was set in a filter holder with a diameter of 100 mm, the inlet side was pressurized with a compressor, the air flow rate was adjusted to 5.3 cm / sec with a flow meter, and the pressure loss at this time was measured with a manometer.

[0341] (coefficient of variation of pressure loss) The standard deviation was calculated from the pressure loss distribution consisting of the pressure losses measured above, and the calculated standard deviation was divided by the average value of the pressure losses at all the measured points to calculate the coefficient of variation. (Coefficient of variation of pressure loss) = (Standard deviation of pressure loss) / (Average pressure loss) x 100 (%)

[0342] (Collection efficiency) According to the method described in JIS B9928 Appendix 5 (Regulations) NaCl aerosol generation method (pressure spray method), NaCl particles generated by an atomizer were classified to a particle size of 0.1 μm using an electrostatic classifier (TSI), and the particle charge was neutralized using americium 241. The permeation flow rate was then adjusted to 5.3 cm / sec. The number of particles before and after the filter material, which was the measurement sample, was determined using a particle counter (TSI, CNC), and the collection efficiency was calculated using the following formula. Collection efficiency (%) = (CO / CI) x 100 CO = Number of 0.1 μm NaCl particles collected by the measurement sample CI = Number of 0.1 μm particles of NaCl supplied to the measurement sample

[0343] Insulated Wire Evaluation (Preparation of coated wire) (i) Preforming 2 kg of the obtained PTFE powder was mixed with 17% by mass (410 g) of an extrusion aid (Isopar H), and the mixture was aged at room temperature for 12 hours. The mixture was then passed through a 10-mesh SUS wire screen in a preformer (manufactured by Tabata Machinery Co., Ltd.) at a ram speed of 100 mm / min, under a pressure of 3 MPa, and at room temperature for 30 minutes to obtain a preformed body. (ii) Paste Extrusion The obtained preform was extruded using a φ50 mm electric wire forming machine (manufactured by Tabata Kikai Kogyo Co., Ltd.) at a ram speed of 33 mm / min and a core wire speed of 23 m / min, using an AWG18 nickel-plated copper wire with an outer diameter of 1.024 mm as the core wire. (iii) Drying and calcination The obtained extrudate was passed through a cabstan set at 160°C, and then passed through a drying furnace set at 200°C, 220°C, and 250°C for drying.The extrudate was then passed through a baking furnace set at 250°C to 460°C for baking at a speed of 23 m / min, and cooled to obtain a coated electric wire with a coating layer thickness of 0.36 mm.

[0344] (Extrusion pressure when forming electric wire) The extrusion pressure was determined by measuring the load when the extrusion load reached equilibrium in the extrusion of (ii) and dividing the load by the cross-sectional area of ​​the cylinder used in forming the electric wire.

[0345] (Wire diameter deviation) In the extrusion of (ii), when the extrusion load reached a balanced state, the insulated electric wire was passed through an outer diameter measuring device (manufactured by Keyence Corporation), and the wire diameter deviation was calculated from the average value and standard deviation of the obtained outer diameter measurements using the following formula. Wire diameter deviation = (standard deviation of outer diameter / average outer diameter) x 100 (%)

[0346] (Spark test) (iii) After drying and baking, the coated wire was passed through a high-frequency spark tester (manufactured by Clinton) to count the number of sparks at an applied voltage of 5 kV.

[0347] (Self-wound heat resistance) A self-winding heat resistance test was carried out in accordance with the self-winding heat resistance described in International Publication No. 2006-054612. Cracks occurring in the wound portion of the covered electric wire were visually observed. Those where cracks occurred were rated as "Bad," and those where no cracks occurred were rated as "Good."

[0348] The following fluorine-containing surfactants having a molecular weight of 1,000 or less were prepared. Perfluoroether carboxylic acid A ammonium salt: Fujifilm Wako Pure Chemical Industries, Ltd., Ammonium perfluoro(2-methyl-3-oxahexanoate), structural formula: CF 3 CF 2 CF 2 OCF(CF 3 )COONH 4 Perfluoroether carboxylic acid B ammonium salt: Perfluoroether carboxylic acid B was purchased from Apollo Scientific Ltd. and used as an ammonium salt. Ammonium perfluoro-3,6-dioxaoctanoate, structural formula: CF 3 CF 2OCF 2 CF 2 OCF 2 COONH 4 Perfluoroether carboxylic acid C ammonium salt: Ammonium 2,3,3,3-tetrafluoro-2-[1,1,2,3,3,3-hexafluoro-2-(trifluoromethoxy)propoxy]-propionate, structural formula: CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COONH 4

[0349] The following hydrophilic monomers were prepared: Hydrophilic monomer D: Ammonium 2,3,3,3-tetrafluoro-2-[(1,1,2-trifluoro-2-propenyl)oxy]- Propanoate, structural formula: CH 2 =CFCF 2 OCF(CF 3 )COONH 4

[0350] Manufacturing Example 1 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3480 g of deionized water, 100 g of paraffin wax, 15.75 g of ammonium salt of perfluoroether carboxylic acid A, and 35 mg of hydrophilic monomer D were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, an aqueous solution of 14.0 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 433 g of TFE was consumed from the start of polymerization, an aqueous solution of 17.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of polymerization of TFE reached 1273 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain PTFE aqueous dispersion A. The average primary particle diameter of the obtained PTFE aqueous dispersion A was 295 nm, and the solid content concentration was 26.5 mass%.

[0351] Comparative Example 1 The PTFE aqueous dispersion A obtained in Production Example 1 was diluted to a solid content concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained PTFE wet powder was placed on a stainless steel flat tray (a tray with no air permeability on the bottom and sides; the same applies below) (amount placed: 2.0 g / cm 2 The flat tray was heat-treated in a hot air circulating electric furnace at 180° C. After 5 hours, the flat tray was taken out and cooled in air to obtain a PTFE powder.

[0352] Comparative Example 2 A PTFE powder was obtained in the same manner as in Comparative Example 1, except that the heat treatment was changed from 5 hours to 20 hours.

[0353] Comparative Example 3 A PTFE powder was obtained in the same manner as in Comparative Example 1, except that the heat treatment temperature was changed from 180°C to 250°C.

[0354] Manufacturing Example 2 3600g of deionized water, 180g of paraffin wax, 5.4g of ammonium salt of perfluoroether carboxylic acid B, 0.108g of succinic acid, and 0.0252g of oxalic acid were charged into a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, and the inside of the polymerization tank was replaced with nitrogen gas while heating to 70°C to remove oxygen. After maintaining the temperature inside the tank at 70°C while stirring, TFE gas was introduced to set the pressure to 2.7MPaG. While stirring the contents, deionized water in which 3.5 mg of potassium permanganate was dissolved was continuously added at a constant rate, and TFE was continuously supplied so that the pressure in the polymerization tank was constant at 2.7 MPaG. When the TFE consumption amount was 184 g, 3.8 g of ammonium salt of perfluoroether carboxylic acid B was added, and when the TFE consumption amount was 900 g, the entire amount of deionized water in which 3.5 mg of potassium permanganate was dissolved was added. When the TFE consumption amount was 1543 g, stirring and TFE supply were stopped, and the TFE in the polymerization tank was purged to terminate the polymerization reaction. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain PTFE aqueous dispersion B. The average primary particle diameter of the obtained PTFE aqueous dispersion B was 310 nm, and the solid content concentration was 30.6 mass%.

[0355] Comparative Example 4 The PTFE aqueous dispersion B obtained in Production Example 2 was diluted to a solid content concentration of 13% by mass, and nitric acid was added as a coagulant while stirring in a container to coagulate the PTFE, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet PTFE powder was placed on a stainless steel flat tray (amount placed: 2.0 g / cm 2 The flat tray was heat-treated in a hot air circulating electric furnace at 210° C. After 18 hours, the flat tray was taken out and cooled in air to obtain a PTFE powder.

[0356] Production Example 3 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3560 g of deionized water, 104 g of paraffin wax, 5.4 g of ammonium salt of perfluoroether carboxylic acid C, and 35 mg of hydrophilic monomer D were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to make the system pressure 0.60 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, 0.60 g of perfluoro (methyl vinyl ether) (PMVE) was injected with TFE. Next, an aqueous solution in which 15 mg of ammonium persulfate was dissolved in 20 g of deionized water was injected with TFE, the system pressure was made 0.78 MPaG, and the polymerization reaction was started. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 429 g of TFE was consumed from the start of polymerization, an aqueous solution of 14 mg of hydroquinone dissolved in 20 g of deionized water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerization reached 1225 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain PTFE aqueous dispersion C. The average primary particle diameter of the obtained PTFE aqueous dispersion C was 234 nm, and the solid content concentration was 25.4 mass%.

[0357] Comparative Example 5 The PTFE aqueous dispersion C obtained in Production Example 3 was diluted to a solid content concentration of 13% by mass, and nitric acid was added as a coagulant while stirring in a container to coagulate the PTFE, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet PTFE powder was placed on a stainless steel flat tray (amount placed: 2.0 g / cm 2 The flat tray was heat-treated in a hot air circulating electric furnace at 210° C. After 18 hours, the flat tray was taken out and cooled in air to obtain a PTFE powder.

[0358] Comparative Example 6 A PTFE powder was obtained in the same manner as in Comparative Example 1, except that the stainless steel flat tray was replaced with a stainless steel mesh tray and the heat treatment at 180° C. for 5 hours was changed to a heat treatment at 200° C. for 1 hour.

[0359] Example 1 A PTFE powder was obtained in the same manner as in Comparative Example 1, except that the stainless steel flat tray was changed to a stainless steel mesh tray. The resulting PTFE powder had an SSG of 2.158.

[0360] Example 2 A PTFE powder was obtained in the same manner as in Example 1, except that the heat treatment was changed from 5 hours to 20 hours.

[0361] Example 3 A PTFE powder was obtained in the same manner as in Comparative Example 4, except that the stainless steel flat tray was replaced with a stainless steel mesh tray and the heat treatment at 210° C. for 18 hours was changed to a heat treatment at 180° C. for 5 hours. The resulting PTFE powder had an SSG of 2.153.

[0362] Example 4 A PTFE powder was obtained in the same manner as in Comparative Example 5, except that the stainless steel flat tray was replaced with a stainless steel mesh tray and the heat treatment at 210° C. for 18 hours was changed to a heat treatment at 180° C. for 20 hours. The PMVE content of the obtained PTFE powder was 0.046 mass %, and the SSG was 2.145.

[0363] The physical properties of each of the PTFE powders (PTFE fine powders) obtained above were measured by the methods described above. The results are shown in Tables 7 to 11.

[0364] [Table 7] [Table 8]

[0365] The results shown in Tables 7 and 8 show that the moisture content exceeds 0.010% by mass when a flat tray is used. In addition, even when a mesh tray is used, the moisture content is high when the heat treatment time is short, at 1 hour. On the other hand, when a mesh tray is used, the moisture content is low at 0.005% by mass or less even with the same heat treatment time as with a flat tray.

[0366] [Table 9] [Table 10] [Table 11] When molding was carried out using the PTFE powder obtained in Comparative Example 1, holes were generated in the unsintered film, and therefore, neither a uniaxially stretched film nor a biaxially stretched film could be obtained.

[0367] Furthermore, in the PTFE powders obtained in Examples 1 to 4, the fluorine-containing compound represented by the following formula was not detected, or the content was 10 ppb by mass or less. F(CF 2 ) 7 COOH, F(CF 2 ) 5 COOH, H(CF 2 ) 6 COOH, H(CF 2 ) 7 COOH, CF 3 O(CF 2 ) 3 OCHFCF 2 COOH, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOH, CF 3 CF 2 CF 2 OCF(CF3 )COOH (perfluoroether carboxylic acid A), CF 3 CF 2 OCF 2 CF 2 OCF 2 COOH (perfluoroether carboxylic acid B), C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOH, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOH (perfluoroether carboxylic acid C), CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOH, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOH, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOH, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOH, and [ka] (In the formula, M is H.)

[0368] Production Example 4 In a 6L stainless steel reactor equipped with a stirrer, 3600g of deionized water, 180g of paraffin wax, 5.4g of ammonium salt of perfluoroether carboxylic acid C, and 26.5mg of oxalic acid were placed. The contents of the reactor were then heated to 70°C while being aspirated, and purged with tetrafluoroethylene (TFE) at the same time to remove oxygen from the reactor, and the contents were stirred. 2.60g of chlorotrifluoroethylene (CTFE) was pressed into the reactor with TFE, and TFE was then added to make the pressure 2.70MPaG. An aqueous solution of potassium permanganate, in which 3.4mg of potassium permanganate was dissolved in deionized water, was continuously added to the reactor as an initiator. After the injection of the initiator, a pressure drop occurred and the start of polymerization was observed. TFE was added to the reactor to keep the pressure constant at 2.70MPaG. When the amount of TFE charged reached 430g, the charging of the aqueous potassium permanganate solution was stopped. When the amount of TFE charged reached 1660 g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was evacuated until it reached normal pressure, and nitrogen replacement was performed, and the contents were removed from the reactor and cooled. The paraffin wax was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 31.4 mass%, and the average primary particle size was 248 nm.

[0369] Example 5 The PTFE aqueous dispersion obtained in Production Example 4 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2 The mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.150 and the CTFE content was 0.100% by mass. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 12.

[0370] Production Example 5 Polymerization was carried out under the same conditions as in Production Example 4, except that the amount of CTFE charged was changed to 1.28 g, the amount of potassium permanganate charged was changed to 3.87 mg, and the final amount of TFE was changed to 1790 g, to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 33.0 mass%, and the average primary particle size was 263 nm.

[0371] Example 6 Using the PTFE aqueous dispersion obtained in Production Example 5, a wet powder was obtained in the same manner as in Example 5. The moisture content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (placement amount: 2.0 g / cm 2 ) and a PTFE powder was obtained in the same manner as in Example 5. The SSG of the obtained PTFE powder was 2.150, and the CTFE content was 0.050 mass%. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 12.

[0372] Production Example 6 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of ammonium salt of perfluoroether carboxylic acid C were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After injecting 0.50 g of HFP with TFE, TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 70 ° C. while stirring. Next, an aqueous solution of 15.4 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 430 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached 1540 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The solid content concentration of the obtained aqueous PTFE dispersion was 29.6 mass%, and the average primary particle size was 246 nm.

[0373] Example 7 The PTFE aqueous dispersion obtained in Production Example 6 was diluted to a solid concentration of 13% by mass, stirred in a container equipped with a stirrer to solidify, and then filtered to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2 ) and the mesh tray was heat-treated in a hot air circulating electric furnace at 180° C. After 18 hours, the mesh tray was taken out and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.146, and the HFP content was 0.019% by mass. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 12.

[0374] Production Example 7 Except for changing the amount of HFP charged to 0.06 g, an aqueous PTFE dispersion was obtained in the same manner as in Production Example 6. The solid content concentration of the obtained aqueous PTFE dispersion was 29.2 mass %, and the average primary particle diameter was 274 nm.

[0375] Example 8 Using the PTFE aqueous dispersion obtained in Production Example 7, a wet powder was obtained in the same manner as in Example 7. The moisture content of the wet powder was about 40 mass %. The obtained wet powder was placed on a stainless steel mesh tray (placement amount: 2.0 g / cm 2 ) and the heat treatment temperature was changed to 160°C, and the same procedure as in Example 7 was repeated to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.154, and the HFP content was 0.002% by mass. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 12.

[0376] Production Example 8 In a 6L stainless steel reactor equipped with a stirrer, 3600g of deionized water, 180g of paraffin wax, and 5.4g of ammonium salt of perfluoroether carboxylic acid C were placed. The reactor contents were then heated to 80°C while being aspirated, and purged with tetrafluoroethylene (TFE) to remove oxygen from the reactor, and the contents were stirred. 3.1g of vinylidene fluoride (VDF) was pressurized into the reactor with TFE, and TFE was then added to make the pressure 2.70MPaG. An aqueous solution of 7.2mg of ammonium persulfate (APS) dissolved in deionized water as an initiator was added to the reactor. After the initiator was injected, a pressure drop occurred and the start of polymerization was observed. TFE was added to the reactor to keep the pressure constant at 2.70MPaG. When the amount of TFE charged reached 430g, an aqueous solution of 18.2mg of hydroquinone dissolved in deionized water was added. When the amount of TFE charged reached 1580 g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was evacuated until it reached normal pressure, and nitrogen replacement was performed, and the contents were removed from the reactor and cooled. The paraffin wax was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 30.3 mass%, and the average primary particle size was 223 nm.

[0377] Example 9 The PTFE aqueous dispersion obtained in Production Example 8 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2The mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.221 and the VDF content was 0.025% by mass. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 12.

[0378] Production Example 9 In a 6L stainless steel reactor equipped with a stirrer, 3600g of deionized water, 180g of paraffin wax, 5.4g of ammonium salt of perfluoroether carboxylic acid C, and 0.0265g of oxalic acid were placed. The contents of the reactor were then heated to 70°C while being aspirated, and purged with tetrafluoroethylene (TFE) at the same time to remove oxygen from the reactor, and the contents were stirred. 1.70g of vinylidene fluoride (VDF) was pressurized into the reactor with TFE, and TFE was then added to make the pressure 2.70MPaG. An aqueous solution of potassium permanganate, in which 3.4mg of potassium permanganate was dissolved in deionized water, was continuously added to the reactor as an initiator. After the injection of the initiator, a pressure drop occurred and the start of polymerization was observed. TFE was added to the reactor to keep the pressure constant at 2.70MPaG. When the amount of TFE charged reached 430g, the charging of the aqueous potassium permanganate solution was stopped. When the amount of TFE charged reached 1815 g, the supply of TFE was stopped, stirring was stopped, and the reaction was terminated. After that, the pressure in the reactor was evacuated until it reached normal pressure, and nitrogen replacement was performed, and the contents were removed from the reactor and cooled. The paraffin wax was removed to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion was 33.3 mass%, and the average primary particle size was 251 nm.

[0379] Example 10 The PTFE aqueous dispersion obtained in Production Example 9 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2The mesh tray was heat-treated in a hot air circulating electric furnace at 210°C. After 18 hours, the mesh tray was removed and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.206, and the VDF content was 0.011% by mass. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 12.

[0380] [Table 12]

[0381] Furthermore, in the PTFE powders obtained in Examples 5 to 10, the fluorine-containing compound represented by the following formula was not detected, or the content was less than 10 ppb by mass. F(CF 2 ) 7 COOH, F(CF 2 ) 5 COOH, H(CF 2 ) 6 COOH, H(CF 2 ) 7 COOH, CF 3 O(CF 2 ) 3 OCHFCF 2 COOH, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOH, CF 3 CF 2 CF 2 OCF(CF 3 )COOH (perfluoroether carboxylic acid A), CF 3 CF 2 OCF 2 CF 2 OCF 2 COOH (perfluoroether carboxylic acid B), C 2 F 5 OCF(CF3 )CF 2 OCF(CF 3 )COOH, CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOH (perfluoroether carboxylic acid C), CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOH, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOH, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOH, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOH, and [ka] (In the formula, M is H.)

[0382] Example 11 A PTFE powder was obtained in the same manner as in Example 1, except that the heat treatment at 180° C. for 5 hours was changed to a heat treatment at 210° C. for 18 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 13 and 14.

[0383] Example 12 A PTFE powder was obtained in the same manner as in Example 1, except that the heat treatment at 180° C. for 5 hours was changed to a heat treatment at 210° C. for 5 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 13 and 14.

[0384] Comparative Example 7 A PTFE powder was obtained in the same manner as in Comparative Example 1, except that the heat treatment at 180° C. for 5 hours was changed to a heat treatment at 210° C. for 18 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 13 and 14.

[0385] Example 13 A PTFE powder was obtained in the same manner as in Example 4, except that the heat treatment at 180° C. for 20 hours was changed to a heat treatment at 210° C. for 18 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 13 and 14.

[0386] Comparative Example 8 A PTFE powder was obtained in the same manner as in Comparative Example 5, except that the heat treatment at 210°C for 5 hours was performed instead of at 210°C for 18 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 13 and 14.

[0387] Manufacturing Example 10 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of ammonium salt of perfluoroether carboxylic acid C were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After injecting 0.11 g of HFP with TFE, TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 70 ° C. while stirring. Next, an aqueous solution of 15.4 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 430 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached 1540 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The solid content concentration of the obtained aqueous PTFE dispersion was 29.8 mass%, and the average primary particle size was 312 nm.

[0388] Example 14 The PTFE aqueous dispersion obtained in Production Example 10 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to separate the water, to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2 The mesh tray was heat-treated in a hot air circulating electric furnace at 180°C. After 18 hours, the mesh tray was removed and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.153 and the HFP content was 0.005% by mass. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 13 and 14.

[0389] [Table 13]

[0390] [Table 14]

[0391] From the results shown in Tables 11, 13, and 14, it can be seen that as the moisture content increases, the extrusion pressure decreases and the coefficient of variation of the extrusion pressure increases. In addition, the appearance of the unsintered film and the PTFE porous membrane deteriorates. When the moisture content was increased beyond 0.1%, holes were formed in the unfired film. It can be seen that as the moisture content increases, the pressure drop of the filter medium decreases, the coefficient of variation of the pressure drop increases, and the pressure drop becomes non-uniform.

[0392] Example 15 A PTFE powder was obtained in the same manner as in Example 1, except that the heat treatment at 135° C. for 18 hours was performed instead of at 180° C. for 5 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 15 and 16.

[0393] Comparative Example 9 A PTFE powder was obtained in the same manner as in Comparative Example 1, except that the heat treatment at 135°C for 18 hours was performed instead of at 180°C for 5 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 15 and 16.

[0394] Manufacturing Example 11 3600g of deionized water, 180g of paraffin wax, and 5.4g of ammonium salt of perfluoroether carboxylic acid C were charged into a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, and the inside of the polymerization tank was replaced with nitrogen gas while heating to 85°C to remove oxygen. After maintaining the temperature inside the tank at 85°C while stirring, TFE gas was introduced to set the pressure at 2.4MPaG. While stirring the contents, deionized water in which 468mg of disuccinic acid peroxide was dissolved was added to start polymerization. As the polymerization proceeded, the pressure inside the polymerization tank decreased, but TFE was continuously fed to keep the pressure constant at 2.4MPaG. When the TFE consumption amount reached 1580g, the stirring and TFE supply were stopped, and the TFE in the polymerization tank was purged to terminate the polymerization reaction. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 294nm, and the solid content was 30.4% by mass.

[0395] Example 16 The PTFE aqueous dispersion obtained in Production Example 11 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2 The mesh tray was heat-treated in a hot air circulating electric furnace at 170°C. After 18 hours, the mesh tray was removed and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.160. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 15 and 16.

[0396] Manufacturing Example 12 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3600 g of deionized water, 180 g of paraffin wax, 5.4 g of ammonium salt of perfluoroether carboxylic acid C, and 0.0252 g of oxalic acid were charged, and the inside of the polymerization tank was replaced with nitrogen gas while heating to 70°C to remove oxygen. After maintaining the temperature inside the tank at 70°C while stirring, TFE gas was introduced to set the pressure at 2.7 MPaG. While stirring the contents, deionized water in which 7.5 mg of potassium permanganate was dissolved was continuously added at a constant rate, and TFE was continuously supplied so that the pressure inside the polymerization tank was constant at 2.7 MPaG. When the TFE consumption amount reached 1730 g, the stirring and the supply of TFE were stopped, and the TFE in the polymerization tank was purged to terminate the polymerization reaction. The aqueous dispersion was taken out and cooled, and then the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the resulting PTFE aqueous dispersion was 296 nm, and the solid content was 32.4% by mass.

[0397] Example 17 The PTFE aqueous dispersion obtained in Production Example 12 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2 The mesh tray was heat-treated in a hot air circulating electric furnace at 180°C. After 18 hours, the mesh tray was removed and cooled in air to obtain a PTFE powder. The SSG of the obtained PTFE powder was 2.156. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 15 and 16.

[0398] [Table 15]

[0399] [Table 16]

[0400] From Example 15 and Comparative Example 9 in Table 15, it can be seen that as the moisture content increases, the extrusion pressure decreases and the pressure loss decreases. Although it is suitable as a HEPA filter medium, as the moisture content increases, the extrusion pressure decreases and the coefficient of variation of the extrusion pressure worsens, as shown in Comparative Example 9. In addition, in the stretched membrane evaluation, the extrusion pressure decreases and the pressure loss of the filter medium worsens. In Examples 16 and 17, the SSG is larger than that of Example 15, and therefore the collection efficiency of the filter medium is lower. However, the pressure loss is low and the coefficient of variation of the pressure loss is small, so that they can be used as filter media.

[0401] Manufacturing Example 13 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of ammonium salt of perfluoroether carboxylic acid C were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 80 ° C. to remove oxygen. After adding 1.20 g of CTFE, TFE was further pressed in to make the system pressure 0.78 MPaG, and the system temperature was maintained at 80 ° C. while stirring. Next, an aqueous solution of 360 mg of disuccinic acid peroxide dissolved in 20 g of water and an aqueous solution of 10 mg of ammonium persulfate dissolved in 20 g of water were pressed in with TFE to start the polymerization reaction. As the polymerization reaction progressed, the pressure in the system decreased, but TFE was added to maintain the system temperature at 80 ° C. and the system pressure at 0.78 MPaG. When 1530g of TFE was consumed from the start of polymerization (conversion rate 90%), 4.2g of CTFE was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerization reached 1700g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 241nm, and the solid content concentration was 32.0% by mass.

[0402] Example 18 The PTFE aqueous dispersion obtained in Production Example 13 was diluted to a solid content concentration of 13% by mass, vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to separate the water, thereby obtaining a wet powder. The obtained wet powder was placed on a stainless steel mesh tray (placement amount: 2.0 g / cm 2 ) and the mesh tray was heat-treated in a hot air circulating electric furnace at 145°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The obtained PTFE powder had an SSG of 2.170 and a CTFE content of 0.23% by mass. The results are shown in Tables 17 to 19.

[0403] Example 19 A PTFE powder was obtained in the same manner as in Example 18, except that the heat treatment at 145° C. for 5 hours was changed from 145° C. for 18 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 17 to 19.

[0404] Comparative Example 10 The PTFE aqueous dispersion obtained in Production Example 13 was diluted to a solid content concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the water was filtered off to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet PTFE powder was placed on a stainless steel flat tray (amount placed: 2.0 g / cm 2 The flat tray was heat-treated in a hot air circulating electric furnace at 145°C for 18 hours. After 18 hours, the flat tray was removed and cooled in air to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 17 to 19.

[0405] Comparative Example 11 A PTFE powder was obtained in the same manner as in Comparative Example 10, except that the heat treatment at 145° C. for 5 hours was changed from 145° C. for 18 hours. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 17 to 19.

[0406] Manufacturing Example 14 A 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket was charged with 3560 g of deionized water, 100 g of paraffin wax, and 0.9 g of ammonium salt of perfluoroether carboxylic acid C, and the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After adding 0.67 g of PPVE and 0.37 g of HFP, TFE was further injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 70 ° C. while stirring. Next, an aqueous solution of 322 mg of disuccinic acid peroxide dissolved in 20 g of water and an aqueous solution of 13 mg of ammonium persulfate dissolved in 20 g of water were injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the pressure in the system decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 160 g of TFE was consumed from the start of polymerization, 4.5 g of ammonium salt of perfluoroether carboxylic acid C was injected with TFE. When 1440 g of TFE was consumed from the start of polymerization (conversion rate 90%), 1.57 g of HFP and 0.5 g of methanol were injected with TFE. The polymerization continued thereafter, and when the amount of polymerization of TFE reached 1600 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle diameter of the obtained aqueous PTFE dispersion was 249 nm, and the solid content concentration was 30.7 mass%.

[0407] Example 20 The PTFE aqueous dispersion obtained in Production Example 14 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2) and the mesh tray was heat-treated in a hot air circulating electric furnace at 145°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The obtained PTFE powder had an SSG of 2.176, a PPVE content of 0.03 mass%, and an HFP content of 0.05 mass%. The results are shown in Tables 17 to 19.

[0408] Comparative Example 12 The same procedure as in Example 20 was repeated, except that the heat treatment in the mesh tray was changed to that in the flat tray. A PTFE powder was obtained. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 17 to 19.

[0409] Manufacturing Example 15 A 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket was charged with 3560 g of deionized water, 100 g of paraffin wax, and 1.2 g of ammonium salt of perfluoroether carboxylic acid C, and the autoclave was replaced with nitrogen gas while heating to 80 ° C. to remove oxygen. After adding 2.6 g of PPVE and 0.67 g of HFP, TFE was further injected to make the system pressure 1.5 MPaG, and the system temperature was maintained at 80 ° C. while stirring. Next, an aqueous solution of 285 mg of disuccinic acid peroxide dissolved in 20 g of water and an aqueous solution of 11 mg of ammonium persulfate dissolved in 20 g of water were injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the pressure in the system decreased, but TFE was added to maintain the system temperature at 80 ° C. and the system pressure at 1.5 MPaG. When 180g of TFE was consumed from the start of polymerization (conversion rate 10%), the supply of TFE and stirring were stopped, followed by slowly releasing gas until the pressure in the system reached 0.1MPaG, after which TFE was supplied until the pressure in the system reached 1.5MPaG, and stirring was started again. At the same time, 4.5g of ammonium salt of perfluoroether carboxylic acid C was injected with TFE. When 1620g of TFE was consumed from the start of polymerization (conversion rate 90%), 5.70g of HFP and 0.17g of methanol were injected with TFE. The polymerization continued thereafter, and when the amount of polymerization of TFE reached 1800g from the start of polymerization, stirring and the supply of TFE were stopped, the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 252nm, and the solid content concentration was 33.2% by mass.

[0410] Example 21 The PTFE aqueous dispersion obtained in Production Example 15 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2) and the mesh tray was heat-treated in a hot air circulating electric furnace at 145°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The obtained PTFE powder had an SSG of 2.176, a PPVE content of 0.03 mass%, and an HFP content of 0.07 mass%. The results are shown in Tables 17 to 19.

[0411] Manufacturing Example 16 A 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket was charged with 3560 g of deionized water, 100 g of paraffin wax, and 1.45 g of ammonium salt of perfluoroether carboxylic acid C, and the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After adding 3.0 g of PPVE, TFE was further injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 70 ° C. while stirring. Next, an aqueous solution of 326 mg of disuccinic acid peroxide dissolved in 20 g of water and an aqueous solution of 12 mg of ammonium persulfate dissolved in 20 g of water were injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the pressure in the system decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 170 g of TFE was consumed from the start of polymerization, 2.2 g of ammonium salt of perfluoroether carboxylic acid C was injected with TFE. When 1530 g of TFE was consumed from the start of polymerization (conversion rate 90%), 0.28 g of methanol was injected with TFE. The polymerization continued thereafter, and when the amount of polymerization of TFE reached 1700 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle diameter of the obtained aqueous PTFE dispersion was 243 nm, and the solid content concentration was 31.6 mass%.

[0412] Example 22 The PTFE aqueous dispersion obtained in Production Example 16 was diluted to a solid content concentration of 13% by mass, and the mixture was vigorously stirred in a container equipped with a stirrer to solidify, and then filtered to separate the water, to obtain a wet powder. The water content of the wet powder was about 40% by mass. The obtained wet powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2 ) and the mesh tray was heat-treated in a hot air circulating electric furnace at 145°C. After 18 hours, the mesh tray was removed and air-cooled to obtain a PTFE powder. Various physical properties of the obtained PTFE powder were measured. The obtained PTFE powder had an SSG of 2.166 and a PPVE content of 0.13% by mass. The results are shown in Tables 17 to 19. Furthermore, the content of the compound having 9 to 14 carbon atoms and represented by general formula (2) in the obtained PTFE powder was below the lower limit of quantification.

[0413] Comparative Example 13 A PTFE powder was obtained in the same manner as in Example 22, except that the heat treatment in the mesh tray was changed to the heat treatment in a flat tray. Various physical properties of the obtained PTFE powder were measured. The results are shown in Tables 17 and 18. In addition, the content of the compound having 9 carbon atoms and represented by general formula (2) in the obtained PTFE powder was 2 ppb by mass, the content of the compound having 11 carbon atoms was 11 ppb by mass, the content of the compound having 13 carbon atoms was 18 ppb by mass, and the contents of the compounds having 10, 12, and 14 carbon atoms were below the lower limit of quantification.

[0414] [Table 17]

[0415] [Table 18]

[0416] From Table 17, it can be seen that as the moisture content increases, the extrusion pressure decreases and the coefficient of variation of the extrusion pressure increases. When the moisture content exceeds 0.1%, the extrusion pressure is unstable and good beads cannot be obtained. In the insulated wire evaluation, it was found that as the moisture content increased, the wire diameter deviation increased, the number of sparks exceeded 10, and the self-winding heat resistance decreased.

[0417] [Table 19]

[0418] Furthermore, in the PTFE powders obtained in Examples 11 to 22, the fluorine-containing compound represented by the following formula was not detected, or the content was 10 ppb by mass or less. F(CF 2 ) 7 COOH, F(CF 2 ) 5 COOH, H(CF 2 ) 6 COOH, H(CF 2 ) 7 COOH, CF 3 O(CF 2 ) 3 OCHFCF 2 COOH, C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOH, CF 3 CF 2 CF 2 OCF(CF 3 )COOH (perfluoroether carboxylic acid A), CF 3 CF 2 OCF 2 CF 2 OCF 2 COOH (perfluoroether carboxylic acid B), C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOH, CF 3OCF(CF 3 )CF 2 OCF(CF 3 )COOH (perfluoroether carboxylic acid C), CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOH, CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOH, CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOH, CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOH, and [ka] (In the formula, M is H.)

Claims

1. A fine powder of a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing 99.0% by mass or more of polymerization units based on tetrafluoroethylene and 1.0% by mass or less of polymerization units based on a modified monomer, A polytetrafluoroethylene fine powder that is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less.

2. 2. The polytetrafluoroethylene fine powder according to claim 1, which is substantially free of any of the fluorine-containing compounds represented by the following formulae: F(CF 2 ) 7 COOM、 F(CF 2 ) 5 COOM、 H(CF 2 ) 6 COOM、 H(CF 2 ) 7 COOM、 CF 3 O(CF 2 ) 3 OCHFCF 2 AOM、 C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM、 C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and, 【Chemistry 1】 (In each formula, M is H, metal atom, NR 1 4 , imidazolium which may have a substituent, pyridinium which may have a substituent, or phosphonium which may have a substituent. 1 is H or an organic group.

3. 3. The polytetrafluoroethylene fine powder according to claim 1, wherein the content of the fluorine-containing compound is less than 25 ppb by mass based on the polytetrafluoroethylene fine powder.

4. A fine powder of a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing 99.0% by mass or more of polymerization units based on tetrafluoroethylene and 1.0% by mass or less of polymerization units based on a modified monomer, The polytetrafluoroethylene fine powder is stretchable, has a standard specific gravity of 2.160 or less, and is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less.

5. A fine powder of a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing 99.0% by mass or more of polymerization units based on tetrafluoroethylene and 1.0% by mass or less of polymerization units based on a modified monomer, A polytetrafluoroethylene fine powder which is stretchable, has a standard specific gravity of 2.160 or less, and is substantially free of both moisture and a fluorine-containing compound represented by the following formula: F(CF 2 ) 7 COOM、 F(CF 2 ) 5 COOM、 H(CF 2 ) 6 COOM、 H(CF 2 ) 7 COOM、 CF 3 O(CF 2 ) 3 OCHFCF 2 AOM、 C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM、 C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and, 【Chemistry 2】 (In each formula, M is H, metal atom, NR 1 4 , imidazolium which may have a substituent, pyridinium which may have a substituent, or phosphonium which may have a substituent. 1 is H or an organic group.

6. 6. The polytetrafluoroethylene fine powder according to claim 4 or 5, which has a breaking strength of 25.0 N or more and 70.0 N or less as measured using an elongated bead obtained in a stretching test at a total elongation rate of 2,400%.

7. 6. The polytetrafluoroethylene fine powder according to claim 4 or 5, which has a breaking strength of 10.0 N or more and less than 25.0 N as measured using an elongated bead obtained in a stretching test at a total elongation rate of 2,400%.

8. 6. The polytetrafluoroethylene fine powder according to claim 4, wherein the extrusion pressure at a reduction ratio of 100 is 18 MPa or less.

9. 6. The polytetrafluoroethylene fine powder according to claim 4, wherein the content of the fluorine-containing compound is less than 25 ppb by mass based on the polytetrafluoroethylene fine powder.

10. 6. The polytetrafluoroethylene fine powder according to claim 4, having a moisture content of 0.010% by mass or less based on the polytetrafluoroethylene fine powder.

11. 6. The polytetrafluoroethylene fine powder according to claim 4 or 5, obtained by polymerization carried out in the presence of a fluorine-containing surfactant.

12. The polytetrafluoroethylene fine powder according to claim 4 or 5, which is an oriented material.

13. A stretched body using the polytetrafluoroethylene fine powder according to claim 4 or 5.

14. The stretched body according to claim 13, which is a porous membrane, a biaxially stretched membrane, or a filter medium.

15. A fine powder of modified polytetrafluoroethylene containing 99.0 mass% or more of polymerization units based on tetrafluoroethylene and 1.0 mass% or less of polymerization units based on a modified monomer, The modified polytetrafluoroethylene fine powder can be paste-extruded, has a standard specific gravity of 2.155 to 2.190, and is substantially free of moisture and fluorine-containing compounds having a molecular weight of 1,000 or less.

16. A fine powder of modified polytetrafluoroethylene containing 99.0 mass% or more of polymerization units based on tetrafluoroethylene and 1.0 mass% or less of polymerization units based on a modified monomer, The modified polytetrafluoroethylene fine powder is paste-extrudable, has a standard specific gravity of 2.155 to 2.190, and is substantially free of both moisture and a fluorine-containing compound represented by the following formula: F(CF 2 ) 7 COOM、 F(CF 2 ) 5 COOM、 H(CF 2 ) 6 COOM、 H(CF 2 ) 7 COOM、 CF 3 O(CF 2 ) 3 OCHFCF 2 AOM、 C 3 F 7 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 CF 2 OCF(CF 3 )COOM、 CF 3 CF 2 OCF 2 CF 2 OCF 2 COOM、 C 2 F 5 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOM、 CF 2 ClCF 2 CF 2 OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF 2 CF 2 OCF 2 CF(CF 3 )OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF(CF 3 )CF 2 OCF 2 COOM、 CF 2 ClCF(CF 3 )OCF 2 CF(CF 3 )OCF 2 COOM, and, 【Chemistry 3】 (In each formula, M is H, metal atom, NR 1 4 , imidazolium which may have a substituent, pyridinium which may have a substituent, or phosphonium which may have a substituent. 1 is H or an organic group.

17. The modified polytetrafluoroethylene fine powder according to claim 15 or 16, wherein the extrusion pressure at a reduction ratio of 1500 is 15 to 80 MPa.

18. 17. The modified polytetrafluoroethylene fine powder according to claim 15 or 16, wherein the content of the fluorine-containing compound is less than 25 ppb by mass based on the modified polytetrafluoroethylene fine powder.

19. 17. The modified polytetrafluoroethylene fine powder according to claim 15 or 16, having a moisture content of 0.010% by mass or less based on the modified polytetrafluoroethylene fine powder.

20. The modified polytetrafluoroethylene fine powder according to claim 15 or 16, obtained by polymerization carried out in the presence of a fluorine-containing surfactant.

21. A molded product using the modified polytetrafluoroethylene fine powder according to claim 15 or 16.

22. The molded article according to claim 21, which is an electric wire covering material or a tube.

23. A fine powder of modified polytetrafluoroethylene containing 99.0 mass% or more of polymerization units based on tetrafluoroethylene and 1.0 mass% or less of polymerization units based on perfluorovinyl ether, The modified polytetrafluoroethylene fine powder is paste extrudable, has a standard specific gravity of 2.135 to 2.200, and is substantially free of both moisture and a fluorine-containing compound represented by general formula (2), and is modified with perfluorovinyl ether. General formula (2): [C n-1 F 2n-1 COO - ] + (wherein n is an integer from 9 to 14; M + represents a cation.)

24. The modified polytetrafluoroethylene fine powder according to claim 23, wherein the amount of modification with perfluorovinyl ether is 0.02% by mass or more and 0.30% by mass or less.

25. The modified polytetrafluoroethylene fine powder according to claim 23 or 24, wherein the extrusion pressure at a reduction ratio of 1500 is 15 to 80 MPa.

26. 25. The modified polytetrafluoroethylene fine powder according to claim 23 or 24, wherein the total content of the fluorine-containing compounds is less than 25 ppb by mass with respect to the modified polytetrafluoroethylene fine powder.

Citation Information

Patent Citations

  • Fluorinated polymer resin treatment using an oxidizing agent to reduce discoloration

    JP2015516029A

  • Method for producing fluoropolymer, polytetrafluoroethylene composition, and polytetrafluoroethylene powder

    WO2021015291A1